Polyamide resin composition, metal resin bonded body and method for producing same, bus bar unit, drive unit

By using a specific ratio of polyamide resin composition and surface roughening treatment technology, the airtightness problem between the polyamide resin composition and the metal member joint in the prior art is solved, and high airtightness and stable performance of hot and cold impact are achieved.

CN119744285APending Publication Date: 2025-04-01MITSUI CHEMICALS INC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380062651.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-02
Filing Date
2023-08-28
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The joint between the conventional polyamide resin composition and the metal member is not high enough in the early stage, and the airtightness is easily reduced when repeated application of hot and cold impacts.

Method used

The polyamide resin composition containing a polyamide resin (A1) having a melting point of 280°C or above, a polyamide resin (A2) having a heat of fusion of 5 J/g or below, a modified polyolefin resin (B) and a nucleating agent (C) was used to optimize the resin composition by differential scanning calorimetry, and the surface roughening treatment was performed on the surface of the metal member to improve bonding strength and airtightness.

Benefits of technology

The high airtightness in the early stage of bonding is achieved, and the airtightness can be fully maintained when repeated cold and hot impacts are applied, and the overall performance of the metal resin bonding is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119744285A_ABST
    Figure CN119744285A_ABST
Patent Text Reader

Abstract

Provided is a polyamide resin composition with which it is possible to produce a metal-resin bonded body that has high airtightness at the initial stage of bonding and that can sufficiently maintain airtightness when hot and cold shocks are repeatedly applied. The polyamide resin composition for bonding to a metal member contains a polyamide resin (A1) having a melting point (Tm) of 280 DEG C or more as measured by differential scanning calorimetry (DSC), a polyamide resin (A2) having a heat of fusion ([delta] H) of 5 J / g or less as measured by differential scanning calorimetry (DSC), a modified polyolefin resin (B), and a nucleating agent (C). The content of the modified polyolefin resin (B) is from 4.70% by mass to 20.00% by mass (inclusive) with respect to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a polyamide resin composition, a metal-resin joint body and a method for producing the same, a bus bar unit, a drive unit and a moving body. Background Art

[0002] Conventionally, polyamide resin compositions have been widely used as materials for various parts such as industrial materials, automobiles, electrical / electronics, and industrial uses, due to their excellent molding processability, mechanical properties, and chemical resistance.

[0003] When the polyamide resin composition is used for these purposes, it is required that the resin component formed by the polyamide resin composition be firmly bonded to the metal component. Therefore, a polyamide resin composition having good bonding properties with metals is being studied. For example, Patent Document 1 states that a polyamide resin composition comprising a polyamide resin having Tm≤290°C, Tm-Tcc≥28°C, and 0J / g<ΔHm≤55J / g and 0.1~10% by mass of talc is well bonded to aluminum.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-132243 Summary of the invention

[0007] Problems to be solved by the invention

[0008] In addition, according to the purpose of the joint body of the polyamide resin composition and the metal component, the air tightness between the polyamide resin composition and the metal component is required. For example, when the above-mentioned joint body is used as a vehicle-mounted product such as a bus bar connected to a drive unit, high air tightness is required to prevent oil leakage. Furthermore, when used for purposes such as vehicle-mounted products, it is also required to maintain sufficient air tightness when repeatedly applying temperature changes (thermal shocks) to low and high temperatures. However, the air tightness of the joint body formed by joining the conventional polyamide resin composition and the metal component recorded in patent document 1 is not high enough at the initial stage of the joint, or the air tightness will be reduced when repeatedly applying thermal shocks.

[0009] In view of these circumstances, the object of the present invention is to provide a polyamide resin composition that can produce a metal-resin joint body that has high airtightness in the initial stage of joining and can fully maintain airtightness when repeated thermal shocks are applied, a metal-resin joint body using the polyamide resin composition and a method for manufacturing the same, and a busbar unit, a drive unit and a movable body using the polyamide resin composition.

[0010] Means for solving problems

[0011] One embodiment of the present invention relates to the polyamide resin composition of the following [1] to [8].

[0012] [1] A polyamide resin composition for bonding to a metal member, comprising a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), wherein the polyamide resin (A) comprises a polyamide resin (A1) having a melting point (Tm) of 280°C or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion (ΔH) of 5 J / g or lower as measured by differential scanning calorimetry (DSC), and the content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

[0013] [2] The polyamide resin composition according to [1], wherein the content of the modified polyolefin resin (B) is 4.70% by mass or more and 12.50% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

[0014] [3] The polyamide resin composition according to [1] or [2], wherein the content of the copper-based heat stabilizer is 0.30 mass % or less based on the total mass of the polyamide resin composition.

[0015] [4] A polyamide resin composition as described in any one of [1] to [3], wherein the polyamide resin (A1) comprises a component unit (A1a) derived from a dicarboxylic acid and a component unit (A1b) derived from a diamine, and the component unit (A1a) derived from a dicarboxylic acid comprises a component unit derived from terephthalic acid and a component unit derived from isophthalic acid.

[0016] [5] The polyamide resin composition according to any one of [1] to [4], wherein the polyamide resin (A) comprises a polyamide resin (A3) having a glass transition temperature (Tg) of 70° C. or less as measured by differential scanning calorimetry (DSC).

[0017] [6] The polyamide resin composition according to [5], wherein the polyamide resin (A3) has a melting point (Tm) of 200° C. or less as measured by differential scanning calorimetry (DSC).

[0018] [7] A polyamide resin composition as described in any one of [1] to [6], wherein the glass transition temperature (Tg) of the polyamide resin (A1) measured by differential scanning calorimetry (DSC) is 75°C to 160°C, and the glass transition temperature (Tg) of the polyamide resin (A2) measured by differential scanning calorimetry (DSC) is 75°C to 160°C.

[0019] [8] The polyamide resin composition according to any one of [1] to [7], wherein the nucleating agent (C) is talc, and the content of the nucleating agent (C) is 0.10 to 5.00% by mass relative to the total mass of the polyamide resin composition.

[0020] Another aspect of the present invention relates to the metal-resin bonded body described in the following [9].

[0021] [9] A metal-resin joint, comprising a metal component and a resin component comprising a polyamide resin composition joined to the surface of the metal component, the polyamide resin composition comprising a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), the polyamide resin (A) comprising a polyamide resin (A1) having a melting point (Tm) of 280°C or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion (ΔH) of 5 J / g or lower as measured by differential scanning calorimetry (DSC), and the content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

[0022] Another aspect of the present invention relates to a method for producing a metal-resin bonded body according to the following

[10] and

[11] .

[0023]

[10] A method for manufacturing a metal-resin joint, comprising the steps of preparing a metal component, bringing a softened or melted polyamide resin composition into contact with a surface of the metal component, and cooling the contacted polyamide resin composition, wherein the polyamide resin composition comprises a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), wherein the polyamide resin (A) comprises a polyamide resin (A1) having a melting point (Tm) of 280° C. or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion (ΔH) of 5 J / g or lower as measured by differential scanning calorimetry (DSC), and wherein the content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

[0024]

[11] The method for producing a metal-resin joint according to

[10] , wherein in the step of preparing the metal member, a surface of the metal member to be joined to the polyamide resin composition is subjected to a surface roughening treatment.

[0025] Another aspect of the present invention relates to the bus bar unit described in the following

[12] .

[0026]

[12] A busbar unit comprising a metal busbar and a retaining member arranged in contact with the busbar and retaining the busbar, the retaining member comprising a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), the polyamide resin (A) comprising a polyamide resin (A1) having a melting point (Tm) of 280°C or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion (ΔH) of 5 J / g or lower as measured by differential scanning calorimetry (DSC), and the content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

[0027] Another aspect of the present invention relates to the drive unit described in the following

[13] .

[0028]

[13] A drive unit comprising: a motor, an inverter for supplying electric power to the motor, and a bus bar unit for electrically connecting the motor and the inverter, wherein the bus bar unit is the bus bar unit described in

[12] .

[0029] Another embodiment of the present invention relates to the moving body described in the following

[14] .

[0030]

[14] A mobile body comprising a body and a driving unit, wherein the driving unit is the driving unit described in

[13] .

[0031] Effects of the Invention

[0032] According to the present invention, there can be provided a polyamide resin composition capable of producing a metal-resin joint body having high airtightness in the initial stage of joining and capable of fully maintaining airtightness when repeated thermal shocks are applied, a metal-resin joint body using the polyamide resin composition and a method for producing the same, and a busbar unit, a drive unit and a movable body using the polyamide resin composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] [ Figure 1 ] Figure 1 It is a schematic diagram showing an exemplary form of a metal-resin joint body as a bus bar unit.

[0034] [ Figure 2 ] Figure 2It is a structural diagram showing an exemplary structure of a moving object (vehicle) having a bus bar unit. DETAILED DESCRIPTION

[0035] 1. First Implementation

[0036] The first embodiment of the present invention relates to a polyamide resin composition for bonding with a metal component. The polyamide resin composition comprises a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C). The polyamide resin composition is suitable as a polyamide resin composition for direct bonding with a metal component having an uneven surface.

[0037] The above-mentioned polyamide resin composition is a resin composition in which the main component of the resin component is a polyamide resin (A). Main component refers to that the proportion shared by the polyamide resin (A) in the resin component is more than 50.00 mass %. The proportion shared by the polyamide resin (A) in the resin component is preferably more than 60.00 mass %, more preferably more than 70.00 mass %. The upper limit of the proportion shared by the polyamide resin (A) in the resin component is not particularly limited, and can be set to less than 100.00 mass %, can be less than 90.00 mass %, or can be less than 80.00 mass %.

[0038] 1-1. Polyamide resin (A)

[0039] The polyamide resin (A) comprises a polyamide resin (A1) having a melting point (Tm) of 280° C. or higher as measured by differential scanning calorimetry (DSC), and a polyamide resin (A2) having a heat of fusion (ΔH) of 5 J / g or lower as measured by differential scanning calorimetry (DSC). The polyamide resin (A) may further comprise a polyamide resin (A3) having a glass transition temperature (Tg) of 70° C. or lower as measured by differential scanning calorimetry (DSC).

[0040] 1-1-1. Polyamide resin (A1)

[0041] The polyamide resin (A1) is a polyamide resin having a melting point (Tm) of 280°C or more as measured by differential scanning calorimetry (DSC). The polyamide resin (A1) may be a polyamide resin comprising a component unit (A1a) derived from a dicarboxylic acid and a component unit (A1b) derived from a diamine. In order to increase the melting point (Tm) and glass transition temperature (Tg) of the polyamide resin (A1), the component unit (A1a) derived from a dicarboxylic acid preferably comprises a component unit derived from an aromatic dicarboxylic acid or an alicyclic dicarboxylic acid. The polyamide resin (A1) improves the bonding strength between the resin component comprising the above-mentioned polyamide resin composition and the metal component. From the viewpoint of further improving bonding strength and airtightness, the polyamide resin (A1) is preferably a crystalline polyamide resin.

[0042] [Component units derived from dicarboxylic acid (A1a)]

[0043] Examples of aromatic dicarboxylic acids include terephthalic acid, naphthalene dicarboxylic acid and their esters. Examples of alicyclic dicarboxylic acids include cyclohexane dicarboxylic acid and its esters. Among them, from the viewpoint of obtaining a polyamide resin with high crystallinity and high heat resistance, the component unit (A1a) derived from dicarboxylic acid preferably includes a component unit derived from an aromatic dicarboxylic acid, and more preferably includes a component unit derived from terephthalic acid.

[0044] The content of the component unit derived from aromatic dicarboxylic acid or alicyclic dicarboxylic acid (preferably a component unit derived from aromatic dicarboxylic acid, more preferably a component unit derived from terephthalic acid) is not particularly limited, and is preferably 50 mol% or more and 100 mol% or less relative to the total molar number of the component unit (A1a) derived from dicarboxylic acid. When the content of the above-mentioned component unit is 50 mol% or more, it is easy to improve the crystallinity of the polyamide resin. From the same viewpoint, the content of the above-mentioned component unit is more preferably 70 mol% or more and 100 mol% or less.

[0045] In the present embodiment, the component unit (A1a) derived from dicarboxylic acid preferably includes the component unit (a1) derived from terephthalic acid, naphthalene dicarboxylic acid or cyclohexane dicarboxylic acid. These component units (a1) can improve the crystallinity of polyamide resin (A1), improve the bonding strength and airtightness of resin component and metal component. From the viewpoint of ensuring the crystallinity of polyamide resin, the content of these component units (a1) is preferably set to be greater than 20 mol% and less than 100 mol% relative to the total mole number of the component unit (A1a) derived from dicarboxylic acid. From the viewpoint of further improving the crystallinity of polyamide resin, the content of these component units (a1) is preferably 45 mol% or more and less than 100 mol% relative to the total mole number of the component unit (A1a) derived from dicarboxylic acid, more preferably 50 mol% or more and less than 99 mol%, more preferably 60 mol% or more and less than 90 mol%, more preferably 60 mol% or more and less than 85 mol%, particularly preferably greater than 60 mol% and less than 80 mol%.

[0046] The component units (A1a) derived from dicarboxylic acid may contain aromatic carboxylic acid component units (a2) other than the above-mentioned component units (a1) or component units (a3) ​​derived from aliphatic dicarboxylic acid having 4 to 20 carbon atoms, within a range not impairing the effects of the present invention.

[0047] The example of the component unit (a2) derived from the aromatic dicarboxylic acid other than terephthalic acid includes the component unit derived from isophthalic acid and 2-methylterephthalic acid, etc. Among them, the component unit derived from isophthalic acid is preferred. From the viewpoint of ensuring the crystallinity of the polyamide resin, when the polyamide resin (A1) contains the component unit (a2), the content of these component units (a2) is preferably 1 mol% or more and 50 mol% or less relative to the total molar number of the component unit (A1a) derived from the dicarboxylic acid, more preferably 10 mol% or more and 40 mol% or less, further preferably 15 mol% or more and 40 mol% or less, and particularly preferably 20 mol% or more and less than 40 mol%.

[0048] The component unit (a3) ​​derived from an aliphatic dicarboxylic acid is a component unit derived from an aliphatic dicarboxylic acid having an alkylene group with a carbon number of 4 or more and 20 or less, and is preferably a component unit derived from an aliphatic dicarboxylic acid having an alkylene group with a carbon number of 6 or more and 12 or less. Examples of the above-mentioned aliphatic dicarboxylic acids include dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyladipic acid, trimethyladipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, suberic acid component units, etc. Among them, adipic acid and sebacic acid are preferred. From the viewpoint of improving the crystallinity of the polyamide resin (A1), when the polyamide resin (A1) contains the component units (a3), the content of these component units (a3) ​​is preferably from 0 mol% to 40 mol%, more preferably from 0 mol% to 20 mol%, further preferably from 1 mol% to 10 mol%, particularly preferably from 1 mol% to 5 mol%, relative to the total molar number of the component units (A1a) derived from dicarboxylic acid.

[0049] The component units (A1a) derived from dicarboxylic acid preferably include component units (a1) derived from terephthalic acid and component units (a2) derived from isophthalic acid. When the component units (A1a) derived from dicarboxylic acid include component units (a2) derived from isophthalic acid in addition to component units (a1) derived from terephthalic acid, the melting point (Tm) of the polyamide resin (A1) can be lowered compared to the case where the component units (A1a) derived from dicarboxylic acid include only component units (a1) derived from terephthalic acid, and the molding processability can be improved.

[0050] The dicarboxylic acid-derived component units (A1a) may contain a small amount of trivalent or higher polycarboxylic acid component units such as trimellitic acid or pyromellitic acid in addition to the above-mentioned component units (a1), component units (a2) and component units (a3). The content of such polycarboxylic acid component units may be 0 mol% or more and 5 mol% or less relative to the total number of moles of the dicarboxylic acid-derived component units (A1a).

[0051] [Component units derived from diamine (A1b)]

[0052] The component units (A1b) derived from diamine preferably include component units (b1) derived from a linear alkylenediamine having 4 to 18 carbon atoms, and may further include component units (b2) derived from an alkylenediamine having 4 to 18 carbon atoms and having a side chain alkyl group, and component units (b3) derived from an alicyclic diamine having 4 to 20 carbon atoms.

[0053] In the component unit (A1b) derived from diamine, the amount of the component unit (b1) derived from the linear alkylenediamine having 4 to 18 carbon atoms is preferably 20 mol% or more and 100 mol% or less, and more preferably 20 mol% or more and 80 mol% or less, relative to the total molar number of the component unit derived from diamine contained in the polyamide resin (A1). When the content of the above-mentioned component unit is 20 mol% or more, it is easy to moderately accelerate the crystallization rate and moderately improve the crystallinity and mechanical strength of the polyamide resin (A1). When the content of the above-mentioned component unit is 100 mol% or less, preferably 80 mol% or less, the crystallization rate of the polyamide resin (A1) will not become too high, so the fluidity during molding is not easily impaired. From the same point of view, the content of the component unit derived from the linear aliphatic diamine is further preferably 30 mol% or more and 60 mol% or less relative to the above total.

[0054] Examples of the component unit (b1) derived from a linear alkylenediamine having 4 to 18 carbon atoms include component units derived from 1,4-diaminobutane, 1,6-diaminohexane, 1,7-diaminoheptane, 1,8-diaminooctane, 1,9-diaminononane, 1,10-diaminodecane, 1,11-diaminoundecane, and 1,12-diaminododecane. Among them, component units derived from 1,6-diaminohexane, 1,8-diaminooctane, 1,10-diaminodecane, and 1,12-diaminododecane are preferred, and component units derived from 1,6-diaminohexane are more preferred. These component units may be contained in a plurality of types in the polyamide resin (A1).

[0055] In addition, the component unit (A1b) derived from diamine may include a component unit (b2) derived from an alkylene diamine having 4 to 18 carbon atoms with a side chain alkyl group or a component unit (b3) derived from an alicyclic diamine having 4 to 20 carbon atoms. At this time, when the total molar number of the component units derived from diamine contained in the polyamide resin (A1) is set to 100 mol%, the amount of the component unit (b2) derived from an alkylene diamine having 4 to 18 carbon atoms with a side chain alkyl group or the component unit (b3) derived from an alicyclic diamine having 4 to 20 carbon atoms is preferably 20 mol% or more and 80 mol% or less. When the content of the above-mentioned component unit is 20 mol% or more, the crystallization rate of the polyamide resin (A1) tends to be moderately slowed down, so it is easy to improve the fluidity during molding. When the content of the above-mentioned component unit is 80 mol% or less, the crystallinity and mechanical strength of the polyamide resin (A1) are not easily damaged. From the same viewpoint, the content of the component unit derived from the branched aliphatic diamine is more preferably 40 mol % or more and 70 mol % or less based on the above total.

[0056] Examples of the component unit (b2) derived from an alkylenediamine having 4 to 18 carbon atoms and having a side chain alkyl group include 1-butyl-1,2-diaminoethane, 1,1-dimethyl-1,4-diaminobutane, 1-ethyl-1,4-diaminobutane, 1,2-dimethyl-1,4-diaminobutane, 1,3-dimethyl-1,4-diaminobutane, 1,4-dimethyl-1,4-diaminobutane, 2,3-dimethyl-1,4-diaminobutane, 2-methyl-1,5-diaminobutane, Pentane, 2,5-dimethyl-1,6-diaminohexane, 2,4-dimethyl-1,6-diaminohexane, 3,3-dimethyl-1,6-diaminohexane, 2,2-dimethyl-1,6-diaminohexane, 2,2,4-trimethyl-1,6-diaminohexane, 2,4,4-trimethyl-1,6-diaminohexane, 2,4-diethyl-1,6-diaminohexane, 2,3-dimethyl-1,7-diaminoheptane, 2,4-dimethyl-1,7-diaminoheptane, 2, 5-dimethyl-1,7-diaminoheptane, 2,2-dimethyl-1,7-diaminoheptane, 2-methyl-4-ethyl-1,7-diaminoheptane, 2-ethyl-4-methyl-1,7-diaminoheptane, 2,2,5,5-tetramethyl-1,7-diaminoheptane, 3-isopropyl-1,7-diaminoheptane, 3-isooctyl-1,7-diaminoheptane, 1,3-dimethyl-1,8-diaminooctane, 1,4-dimethyl-1,8-diaminooctane, 2,4-dimethyl -1,8-diaminooctane, 3,4-dimethyl-1,8-diaminooctane, 4,5-dimethyl-1,8-diaminooctane, 2,2-dimethyl-1,8-diaminooctane, 3,3-dimethyl-1,8-diaminooctane, 4,4-dimethyl-1,8-diaminooctane, 3,3,5-trimethyl-1,8-diaminooctane, 2,4-diethyl-1,8-diaminooctane and 5-methyl-1,9-diaminononane, 2,2-dimethylpropylenediamine and the like component units. Among them, component units derived from side chain alkyl diamines having 1 to 2 side chain alkyl groups with 1 to 2 carbon atoms and 4 to 10 carbon atoms in the main chain are preferred, and component units derived from 2-methyl-1,5-diaminopentane are more preferred. These component units may contain multiple types in the polyamide resin (A1).

[0057] Examples of the component unit (b3) derived from an alicyclic diamine having 4 to 20 carbon atoms include 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, isophoronediamine, piperazine, 2,5-dimethylpiperazine, bis(4-aminocyclohexyl)methane, bis(4-aminocyclohexyl)propane, 4,4'-diamino-3,3'-dimethyldicyclohexylpropane, 4,4'-diamino-3,3'-dimethyldicyclohexylmethane. , 4,4'-diamino-3,3'-dimethyl-5,5'-dimethyldicyclohexylmethane, 4,4'-diamino-3,3'-dimethyl-5,5'-dimethyldicyclohexylpropane, α,α'-bis(4-aminocyclohexyl)-p-diisopropylbenzene, α,α'-bis(4-aminocyclohexyl)-m-diisopropylbenzene, α,α'-bis(4-aminocyclohexyl)-1,4-cyclohexane, α,α'-bis(4-aminocyclohexyl)-1,3-cyclohexane, bis(aminomethyl)norbornane and the like. Among these, preferred are component units derived from 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(4-aminocyclohexyl)methane, 4,4′-diamino-3,3′-dimethyldicyclohexylmethane, and bis(aminomethyl)norbornane; more preferred are component units derived from 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 1,3-bis(aminocyclohexyl)methane, 1,3-bis(aminomethyl)cyclohexane, and bis(aminomethyl)norbornane; and particularly preferred are component units derived from 1,3-bis(aminomethyl)cyclohexane and bis(aminomethyl)norbornane.

[0058] In addition, in this specification, the number of carbon atoms in the component unit derived from the alkylenediamine having a side chain alkyl group is the total number of carbon atoms of the main chain alkylene group and the number of carbon atoms of the side chain alkyl group unless otherwise specified.

[0059] The polyamide resin (A1) may contain a small amount of component units derived from other diamines such as component units derived from meta-xylylenediamine in addition to the component units (b1) derived from a linear alkylenediamine having 4 to 18 carbon atoms, the component units (b2) derived from an alkylenediamine having 4 to 18 carbon atoms and having a side chain alkyl group, and the component units (b3) derived from an alicyclic diamine having 4 to 20 carbon atoms. The content of such component units derived from other diamines may be 50 mol% or less, preferably 40 mol% or less, relative to the total amount of the component units (A1b) derived from diamines.

[0060] From the viewpoint of improving the thermal stability of the composite during molding and further improving the mechanical strength, the terminal groups of at least a part of the molecules of the polyamide resin (A1) may be capped with an end-capping agent. For example, when the molecular ends are carboxyl groups, the end-capping agent is preferably a monoamine, and when the molecular ends are amino groups, the end-capping agent is preferably a monocarboxylic acid.

[0061] Examples of monoamines include aliphatic monoamines such as methylamine, ethylamine, propylamine, and butylamine; alicyclic monoamines such as cyclohexylamine and dicyclohexylamine; and aromatic monoamines such as aniline and toluidine. Examples of monocarboxylic acids include aliphatic monocarboxylic acids having a carbon number of 2 or more and 30 or less such as acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecanoic acid, myristic acid, palmitic acid, stearic acid, oleic acid, and linoleic acid; aromatic monocarboxylic acids such as benzoic acid, methylbenzoic acid, naphthoic acid, methylnaphthoic acid, and phenylacetic acid; and alicyclic monocarboxylic acids such as cyclohexanecarboxylic acid. The aromatic monocarboxylic acid and the alicyclic monocarboxylic acid may have a substituent in the cyclic structure portion.

[0062] [physical properties]

[0063] The melting point (Tm) of the polyamide resin (A1) may be 280° C. to 340° C. or less. When the melting point (Tm) of the polyamide resin (A1) is 280° C. or more, the mechanical strength and heat resistance of the resin composition and the molded body in the high temperature region are not easily impaired. When the melting point (Tm) is 340° C. or less, there is no need to excessively increase the molding temperature, so the molding processability of the resin composition is easily improved. From the above viewpoints, the melting point (Tm) of the polyamide resin is more preferably 290° C. to 340° C. or less.

[0064] The polyamide resin (A1) can set the glass transition temperature (Tg) to be higher than 70°C and lower than 160°C, preferably to be higher than 75°C and lower than 160°C. Thus, even if the mold temperature is not excessively increased during the molding process, the fluidity of the resin composition can be easily maintained, and the molding processability can be improved. By maintaining the fluidity of the resin composition during the molding process, the resin composition can be fully impregnated in the concavo-convex surface of the metal component, so that the resin composition is fully adhered to the above-mentioned concavo-convex. As a result, the bonding strength between the metal component and the resin component can be further improved, and the airtightness can be further improved.

[0065] The heat of fusion (ΔH) of the polyamide resin (A1) is preferably 20 J / g or more. When the heat of fusion (ΔH) of the polyamide resin (A1) is 20 J / g or more, the crystallinity is improved, so the heat resistance and bonding strength of the resin component are easily improved. It should be noted that the upper limit of the heat of fusion (ΔH) of the polyamide resin (A1) is not particularly limited, and from the viewpoint of improving molding processability, it can be 130 J / g. The heat of fusion (ΔH) of the polyamide resin (A1) is preferably 30 J / g or more and 130 J / g or less, more preferably 30 J / g or more and 100 J / g or less.

[0066] The heat of fusion (ΔH), melting point (Tm), and glass transition temperature (Tg) of the polyamide resin can be measured using a differential scanning calorimeter (DSC220 C model, manufactured by Seiko Instruments).

[0067] Specifically, about 5 mg of crystalline polyamide resin was sealed in an aluminum pan for measurement and heated from room temperature to 350°C at 10°C / min. In order to completely melt the resin, it was kept at 350°C for 3 minutes, and then cooled to 30°C at 10°C / min. After being placed at 30°C for 5 minutes, it was heated to 350°C for the second time at 10°C / min. The temperature (°C) of the endothermic peak in the second heating was taken as the melting point (Tm) of the crystalline polyamide resin, and the displacement point corresponding to the glass transition was taken as the glass transition temperature (Tg). The heat of fusion (ΔH) was calculated according to JIS K7122 (2012) from the area of ​​the endothermic peak during melting during the first heating process.

[0068] The melting point (Tm), glass transition temperature (Tg) and heat of fusion (ΔH) of the polyamide resin (A1) can be adjusted, for example, by the composition of the dicarboxylic acid-derived component unit (A1a), the number of carbon atoms per diamine-derived component unit (A1b), etc. In order to increase the melting point of the polyamide resin (A1), for example, the content ratio of the terephthalic acid-derived component unit can be increased.

[0069] The intrinsic viscosity [η] of the polyamide resin (A1) measured at a temperature of 25°C and in 96.5% sulfuric acid is preferably 0.6 dl / g or more and 1.5 dl / g or less. When the intrinsic viscosity [η] of the polyamide resin (A1) is 0.6 dl / g or more, it is easy to fully improve the mechanical strength (toughness, etc.) of the molded body, and when it is 1.5 dl / g or less, the fluidity of the resin composition during molding is not easily impaired. From the same point of view, the intrinsic viscosity [η] of the polyamide resin (A1) is more preferably 0.8 dl / g or more and 1.2 dl / g or less. The intrinsic viscosity [η] can be adjusted by the end-capping amount of the polyamide resin (A1), etc.

[0070] The intrinsic viscosity of the polyamide resin can be measured according to JIS K6810 (1977). Specifically, 0.5 g of the polyamide resin (A1) is dissolved in 50 ml of a 96.5% sulfuric acid solution to prepare a sample solution. The flow time of the sample solution can be measured at 25±0.05°C using an Ubbelohde viscometer, and the obtained value is substituted into the following formula to calculate.

[0071] [η]=ηSP / [C(1+0.205ηSP)]

[0072] In the above formula, each number or variable represents the following.

[0073] [η]: Intrinsic viscosity (dl / g)

[0074] ηSP: specific viscosity

[0075] C: Sample concentration (g / dl)

[0076] ηSP is obtained by the following formula.

[0077] ηSP=(t-t0) / t0

[0078] t: Number of seconds for the sample solution to flow down (seconds)

[0079] t0: Number of seconds for blank sulfuric acid to flow (seconds)

[0080] [Manufacturing method]

[0081] Polyamide resin (A1) can be manufactured, for example, by polycondensing the aforementioned dicarboxylic acid and the aforementioned diamine in a uniform solution. Specifically, it can be prepared by heating dicarboxylic acid and diamine in the presence of a catalyst to obtain a low-level condensate, and then polycondensing it by applying shear stress to the molten product of the low-level condensate as described in International Publication No. 03 / 085029. It should be noted that at least a portion of the dicarboxylic acid as the raw material of the polyamide resin (A1) can be a dicarboxylic acid derived from biomass, and at least a portion of the diamine can also be a diamine derived from biomass. That is, polyamide resin (A1) can be a polyamide resin derived from biomass, which is obtained by polymerizing a raw material group containing a raw material derived from biomass.

[0082] The terminal blocking agent may be added to the reaction system from the viewpoint of adjusting the intrinsic viscosity of the polyamide resin (A1), etc. The intrinsic viscosity [η] (or molecular weight) of the polyamide resin (A1) can be adjusted by the amount of the terminal blocking agent added.

[0083] The end-capping agent is added to the reaction system of dicarboxylic acid and diamine in an amount of preferably 0.07 mol or less, more preferably 0.05 mol or less, relative to 1 mol of the total amount of dicarboxylic acid.

[0084] The content of polyamide resin (A1) is preferably 25.00 mass % or more and 80.00 mass % or less relative to the gross mass of polyamide resin composition, preferably 30.00 mass % or more and 80.00 mass % or less, more preferably 35.00 mass % or more and 80.00 mass % or less, further preferably 40.00 mass % or more and 80.00 mass % or less. The more the content of polyamide resin (A1) is, the more the bonding strength of resin component and metal component can be further improved. On the other hand, in order to leave room for the effect of further improving the bonding strength and the effect of improving the airtightness by adding other components to delay the crystallization rate, the upper limit of polyamide resin (A1) can be set to above-mentioned range.

[0085] 1-1-2. Polyamide resin (A2)

[0086] Polyamide resin (A2) is a polyamide resin having a melting heat (ΔH) of less than 5J / g as measured by differential scanning calorimetry (DSC). The crystallinity of polyamide resin (A2) is lower than that of polyamide resin (A1), so that the crystallization rate of the resin composition during the molding of the resin component can be delayed. Thus, the resin composition constituting the resin component can be fully flowed along the concavo-convex of the metal component surface, so that the resin composition is fully fitted to the above-mentioned concavo-convex. Therefore, it is believed that polyamide resin (A2) can further improve the bonding strength of the metal component and the resin component, and further improve air tightness.

[0087] The polyamide resin (A2) preferably has substantially no measurable melting point (Tm) in differential scanning calorimetry (DSC). “Substantially no measurable melting point (Tm)” means that substantially no shift point corresponding to the melting point is observed in the above-mentioned measurement method.

[0088] The polyamide resin (A2) can set the glass transition temperature (Tg) to be higher than 70°C and lower than 160°C, preferably to be higher than 75°C and lower than 160°C. Thus, even if the mold temperature is not excessively increased during the molding process, the fluidity of the resin composition can be easily maintained, and the molding processability can be improved. By maintaining the fluidity of the resin composition during the molding process, the resin composition can be fully impregnated in the concavo-convex surface of the metal component, so that the resin composition is fully adhered to the above-mentioned concavo-convex. As a result, the bonding strength between the metal component and the resin component can be further improved, and the airtightness can be further improved.

[0089] The heat of fusion (ΔH) of the polyamide resin (A2) is 5 J / g or less, more preferably 0 J / g. When the heat of fusion (ΔH) of the polyamide resin (A2) is 5 J / g or less, the crystallinity is moderately low, so the crystallization rate of the resin composition during the molding of the resin member can be more fully delayed. The polyamide resin (A2) preferably shows amorphous properties. The heat of fusion (ΔH) can be measured by the same method as described above.

[0090] The polyamide resin (A2) may be a polyamide resin containing a component unit (A2a) derived from a dicarboxylic acid and a component unit (A2b) derived from a diamine.

[0091] [Component units derived from dicarboxylic acid (A2a)]

[0092] The component unit (A2a) derived from a dicarboxylic acid preferably contains at least a component unit derived from isophthalic acid. The component unit derived from isophthalic acid can reduce the crystallinity of the polyamide resin (A2).

[0093] The content of the component unit derived from isophthalic acid is preferably 40 mol% or more, more preferably 50 mol% or more relative to the total amount of the component unit (A2a) derived from dicarboxylic acid. When the content of the component unit derived from isophthalic acid is 40 mol% or more, it is easy to make the polyamide resin (A2) amorphous. The upper limit of the content of the component unit derived from isophthalic acid is not particularly limited, and can be set to 100 mol% or less, preferably set to 90 mol% or less.

[0094] The component unit (A2a) derived from dicarboxylic acid may further contain component units derived from other dicarboxylic acids other than the component unit derived from isophthalic acid within the range that does not impair the effect of the present invention. Examples of other dicarboxylic acids include aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and alicyclic dicarboxylic acids other than isophthalic acid such as terephthalic acid, 2-methylterephthalic acid, and naphthalene dicarboxylic acid. Aliphatic dicarboxylic acids and alicyclic dicarboxylic acids may be the same as the aforementioned aliphatic dicarboxylic acids and alicyclic dicarboxylic acids, respectively. Among them, aromatic dicarboxylic acids other than isophthalic acid are preferred, and terephthalic acid is more preferred.

[0095] In the component unit (A2a) derived from dicarboxylic acid, the molar ratio of the component unit derived from isophthalic acid to the component unit derived from an aromatic dicarboxylic acid other than isophthalic acid (preferably terephthalic acid) is preferably 55 / 45 to 100 / 0 (molar ratio), and more preferably 60 / 40 to 90 / 10 (molar ratio). If the amount of the component unit derived from isophthalic acid is above a certain amount, the polyamide resin (A2) is easy to become amorphous, and the crystallization rate of the resin composition during the molding of the resin component is easily delayed, thereby further improving the bonding strength between the metal component and the resin component and further improving the airtightness.

[0096] [Component units derived from diamine (A2b)]

[0097] The component unit (A2b) derived from a diamine preferably contains a component unit derived from an aliphatic diamine having 4 to 15 carbon atoms.

[0098] The aliphatic diamine having 4 to 15 carbon atoms is the same as the aliphatic diamine having 4 to 15 carbon atoms in the aforementioned diamine-derived component unit (A1b), and is preferably hexamethylenediamine.

[0099] The content of the component unit derived from the aliphatic diamine having 4 to 15 carbon atoms is preferably 50 mol % or more, more preferably 60 mol % or more, based on the total amount of the component units (A2b) derived from diamines.

[0100] The component unit (A2b) derived from diamines may further include component units derived from other diamines other than the component units derived from aliphatic diamines having 4 to 15 carbon atoms, within the range not impairing the effect of the present invention. Examples of other diamines include alicyclic diamines and aromatic diamines. The alicyclic diamines and aromatic diamines may be the same as the aforementioned alicyclic diamines and aromatic diamines, respectively. The content of other diamine component units may be 50 mol % or less, preferably 40 mol % or less.

[0101] Specific examples of the polyamide resin (A2) include polycondensates of isophthalic acid / terephthalic acid / 1,6-hexanediamine / bis(3-methyl-4-aminocyclohexyl)methane, polycondensates of isophthalic acid / bis(3-methyl-4-aminocyclohexyl)methane / ω-laurolactam, polycondensates of isophthalic acid / terephthalic acid / 1,6-hexanediamine, and polycondensates of isophthalic acid / 2,2,4-trimethyl-1,6- Condensation products of hexamethylenediamine / 2,4,4-trimethyl-1,6-hexamethylenediamine, polycondensates of isophthalic acid / terephthalic acid / 2,2,4-trimethyl-1,6-hexamethylenediamine / 2,4,4-trimethyl-1,6-hexamethylenediamine, polycondensates of isophthalic acid / bis(3-methyl-4-aminocyclohexyl)methane / ω-laurolactam, and polycondensates of isophthalic acid / terephthalic acid / other diamine components, etc. Among them, polycondensates of isophthalic acid / terephthalic acid / 1,6-hexamethylenediamine are preferred. The polyamide resin (A2) may contain only one type, or may contain two or more types.

[0102] The intrinsic viscosity [η] of the polyamide resin (A2) measured in 96.5% sulfuric acid at a temperature of 25° C. is preferably 0.4 dl / g or more and 1.6 dl / g or less, and more preferably 0.5 dl / g or more and 1.2 dl / g or less. The intrinsic viscosity [η] of the polyamide resin (A2) can be measured by the same method as the intrinsic viscosity [η] of the polyamide resin (A1).

[0103] The polyamide resin (A2) can be produced by the same method as that of the polyamide resin (A1).

[0104] The content of polyamide resin (A2) is preferably 5.00 mass % or more, more preferably 10.00 mass % or more, and further preferably 15.00 mass % or more relative to the gross mass of polyamide resin composition. By making the content of polyamide resin (A2) be the above-mentioned range, the effect of bonding strength and air tightness improvement brought by the delay of crystallization can be more fully brought into play. The upper limit of the content of polyamide resin (A2) is not particularly limited, and from the viewpoint of coordinating a sufficient amount of polyamide resin (A1) in resin combination, it can be set to below 30.00 mass %, or below 25.00 mass %.

[0105] 1-1-3. Polyamide resin (A3)

[0106] Polyamide resin (A3) is a polyamide resin having a glass transition temperature (Tg) of less than 70°C as measured by differential scanning calorimetry (DSC). The glass transition temperature (Tg) of polyamide resin (A3) is lower than that of polyamide resin (A1). Therefore, when the temperature of the resin composition is reduced during the molding of the resin component, the fluidity of polyamide resin (A3) is less likely to be reduced than that of polyamide resin (A1), and the reduction in the fluidity of the resin composition as a whole can be suppressed. Thus, the resin composition constituting the resin component can be fully flowed along the concavo-convex surface of the metal component, so that the resin composition is fully adhered to the above-mentioned concavo-convex. Therefore, it is believed that polyamide resin (A3) can further improve the bonding strength between the metal component and the resin component, and further improve the airtightness.

[0107] The polyamide resin (A3) can be an aliphatic polyamide containing a component unit having an amide bond (-NH-C(=O)-) and having no aromatic ring (an amide bond-containing component unit having no aromatic ring). The content of the component unit is preferably 80 mol% or more, more preferably 90 to 100 mol%, relative to the total number of moles of the amide bond-containing component units constituting the polyamide resin (A3).

[0108] The polyamide resin (A3) as an aliphatic polyamide may be a polyamide resin obtained by polycondensing a dicarboxylic acid and a diamine, a polyamide resin obtained by polycondensing an aminocarboxylic acid, or a polyamide resin obtained by ring-opening polymerization of a lactam. That is, the polyamide resin (A3) as an aliphatic polyamide is composed of at least one of a component unit containing an amide bond composed of a component unit (A3a) derived from a dicarboxylic acid and a component unit (A3b) derived from a diamine, a component unit (A3c) derived from an aminocarboxylic acid, and a component unit (A3d) derived from a lactam.

[0109] [Component units derived from dicarboxylic acid (A3a)]

[0110] The component unit (A3a) derived from a dicarboxylic acid includes a component unit derived from an aliphatic dicarboxylic acid. The aliphatic dicarboxylic acid is preferably an aliphatic dicarboxylic acid having 2 to 14 carbon atoms, more preferably an aliphatic dicarboxylic acid having 4 to 14 carbon atoms. Examples of aliphatic dicarboxylic acids include oxalic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, and tetradecanedioic acid. Among them, adipic acid, sebacic acid, and dodecanedioic acid are preferred.

[0111] The content of the component units derived from an aliphatic dicarboxylic acid is preferably 80 mol% or more, more preferably 90 to 100 mol%, based on the total number of moles of the component units (e1) derived from a dicarboxylic acid.

[0112] [Component units derived from diamine (A3b)]

[0113] The component unit (A3b) derived from a diamine includes a component unit derived from an aliphatic diamine. As the aliphatic diamine, the same aliphatic diamine as that constituting the polyamide resin (A1) can be used.

[0114] The content of the component unit derived from an aliphatic diamine is preferably 80 mol% or more, more preferably 90 to 100 mol%, based on the total number of moles of the component unit (A3b) derived from a diamine.

[0115] [Component units derived from aminocarboxylic acid (A3c)]

[0116] The aminocarboxylic acid may be an aminocarboxylic acid having 6 to 12 carbon atoms, and preferably an aminocarboxylic acid having 6 to 10 carbon atoms. Examples of such aminocarboxylic acids include 6-aminocaproic acid, 7-aminoheptanoic acid, 11-aminoundecanoic acid, and 12-aminododecanoic acid.

[0117] [Lactam-derived component unit (A3d)]

[0118] The lactam may be a lactam having 6 to 12 carbon atoms, and preferably a lactam having 6 to 10 carbon atoms. Examples of such lactams include α-pyrrolidone, ε-caprolactam, undecanolactam, and ω-laurolactam.

[0119] Examples of the polyamide resin (A3) which is an aliphatic polyamide include polyamide 6, polyamide 66, polyamide 610, polyamide 12, and the like.

[0120] The melting point (Tm) of the polyamide resin (A3) measured by differential scanning calorimetry (DSC) is preferably 270° C. or less, more preferably 100° C. or more and 250° C. or less, and further preferably 120° C. or more and 220° C. or less. The melting point (Tm) of the polyamide resin (A1) can be measured by the same method as the melting point (Tm) of the polyamide resin (A1) described above.

[0121] The polyamide resin (A3) can be produced by a known method.

[0122] The content of polyamide resin (A3) is preferably 1.00% by mass or more and 10.00% by mass or less relative to the total mass of the polyamide resin composition. When the amount of polyamide resin (A3) is more than a certain amount, the bonding strength between the metal component and the resin component can be further improved, and the air tightness during the initial and repeated application of hot and cold shocks can be further improved. When aliphatic polyamide (D) is less than a certain amount, it is easy to improve the resin strength, improve the bonding strength and air tightness. From the above viewpoint, the above content of polyamide resin (A3) is more preferably 1.00% by mass or more and 8.00% by mass or less, and more preferably 3.00% by mass or more and 5.50% by mass or less.

[0123] 1-2. Modified polyolefin resin (B)

[0124] The polyamide resin composition contains a modified polyolefin resin (B) in addition to the polyamide resin (A). The modified polyolefin resin (B) reduces the elastic modulus of the polyamide resin composition and imparts flexibility to the resin component. By using the modified polyolefin resin (B) to make the resin component soft, it is not easy to produce expansion and contraction of the resin component when repeated thermal shocks are applied, and cracks and peeling of the resin component caused by stress generated by the difference in linear expansion coefficient between the metal component. Therefore, it is believed that the modified polyolefin resin (B) can better maintain the airtightness when repeated thermal shocks are applied.

[0125] In addition, the crystallization rate of the resin composition when the modified polyolefin resin (B) can make the resin component molding is reduced, and the crystallization is delayed. Thus, the resin composition constituting the resin component can be fully flowed along the concavo-convex of the metal component surface, so that the resin composition is fully close to the above-mentioned concavo-convex. Therefore, it is believed that the modified polyolefin resin (B) can further improve the bonding strength of the metal component and the resin component, and further improve air tightness.

[0126] The modified polyolefin resin (B) is an olefin polymer having a polyolefin unit and a functional group structural unit. Examples of the functional group possessed by the functional group structural unit include: a functional group containing a heteroatom, an aromatic hydrocarbon group, etc. Preferably, the modified polyolefin resin (B) is a modified olefin polymer having a polyolefin unit and a structural unit containing a functional group containing a heteroatom (functional group structural unit).

[0127] The heteroatom is preferably oxygen. Functional groups containing heteroatoms include ester groups, ether groups, carboxylic acid groups (including carboxylic acid anhydride groups), aldehyde groups, ketone groups, and the like.

[0128] In the modified polyolefin resin (B), it is preferred to contain 0.1 to 5.0% by mass of the functional group structural unit relative to 100% by mass of the modified polyolefin resin (B). The content of the functional group structural unit contained in the modified polyolefin resin (B) is preferably 0.2 to 3.0% by mass, preferably 0.2 to 2.0% by mass. When the amount of the functional group structural unit is within the above range, the impact resistance and elongation of the resin composition are easily improved.

[0129] The content of the functional group structural unit contained in the modified polyolefin resin (B) can be determined by the charging ratio when an olefin polymer and an organic compound containing a functional group are reacted in the presence of a radical initiator, etc., 13 C NMR determination, 1 The identification can be performed by known means such as H NMR measurement. Specific NMR measurement conditions include the following conditions.

[0130] 1 H NMR measurement can be performed under the following conditions: using a nuclear magnetic resonance apparatus ECX400 manufactured by JEOL Ltd., the solvent is deuterated o-dichlorobenzene, the sample concentration is 20 mg / 0.6 mL, the measurement temperature is 120°C, and the observed nucleus is 1 H (400 MHz), sequence is single pulse, pulse width is 5.12 μs (45° pulse), repetition time is 7.0 s, and the number of accumulations is more than 500. Regarding the reference chemical shift, the hydrogen of tetramethylsilane is set to 0 ppm, but the same result can be obtained by setting the peak of residual hydrogen derived from deuterated o-dichlorobenzene to 7.10 ppm as the reference value of the chemical shift. It should be noted that the peak derived from the functional group-containing compound 1 The peaks of H, etc. can be assigned by conventional methods.

[0131] 13 C NMR measurement can be carried out under the following conditions: the measurement device is an ECP500 nuclear magnetic resonance device manufactured by JEOL Ltd., the solvent is a mixed solvent of o-dichlorobenzene / deuterated benzene (80 / 20 volume %), the measurement temperature is 120°C, and the observation nucleus is 13 C (125 MHz), single pulse proton decoupling, 45° pulse, repetition time of 5.5 seconds, cumulative number of more than 10,000 times, 27.50 ppm as the reference value of chemical shift. The allocation of various signals is carried out according to conventional methods, and quantification can be performed based on the cumulative value of signal intensity.

[0132] On the other hand, the skeleton of the modified polyolefin resin (B) is preferably a structure derived from polyolefin, preferably a known olefin polymer such as an ethylene polymer, a propylene polymer, a butene polymer, and a copolymer of these olefins. The skeleton of the above-mentioned olefin polymer is more preferably a copolymer of ethylene and an α-olefin having more than 3 carbon atoms (hereinafter also referred to as "ethylene-α-olefin copolymer"). It should be noted that the olefin polymer may be an olefin polymer derived from biomass, at least a portion of which contains a raw material derived from biomass.

[0133] Examples of the above-mentioned α-olefins having 3 or more carbon atoms include propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, and 1-decene. Specific examples of the above-mentioned ethylene-α-olefin copolymers include ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, and ethylene-4-methyl-1-pentene copolymers. Among them, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-4-methyl-1-pentene copolymers, ethylene-1-hexene copolymers, and ethylene-1-octene copolymers are preferred.

[0134] When the total molar number of the structural units contained in the ethylene-α-olefin copolymer is set to 100 mol%, the ethylene-α-olefin copolymer preferably contains the structural units derived from ethylene in an amount of 70 to 99.5 mol%, and more preferably contains the structural units derived from ethylene in an amount of 80 to 99 mol%. In addition, when the total molar number of the structural units contained in the ethylene-α-olefin copolymer is set to 100 mol%, the ethylene-α-olefin copolymer preferably contains the structural units derived from α-olefin in an amount of 0.5 to 30 mol%, and more preferably contains them in an amount of 1 to 25 mol%.

[0135] The melt flow rate (MFR) of the ethylene-α-olefin copolymer at 190° C. and a load of 2.16 kg according to ASTM D1238 is preferably 0.01 to 20 g / 10 min, more preferably 0.05 to 20 g / 10 min, and further preferably 0.1 to 10 g / 10 min.

[0136] The modified polyolefin resin (B) can be obtained, for example, by reacting the above-mentioned olefin polymer with the above-mentioned compound having a functional group at a specific ratio.

[0137] Preferred examples of the functional group-containing compound that reacts with the olefin polymer include unsaturated carboxylic acids and their derivatives. Specifically, the functional group-containing compound includes unsaturated carboxylic acids such as acrylic acid, methacrylic acid, α-ethyl acrylic acid, maleic acid, fumaric acid, itaconic acid, citraconic acid, tetrahydrophthalic acid, methyltetrahydrophthalic acid, endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid (nadic acid [trademark]), and their acyl halides, amides, imides, anhydrides, esters, and the like. Among them, unsaturated dicarboxylic acids or their anhydrides are preferred, and maleic acid, nadic acid (trademark) or their anhydrides are particularly preferred.

[0138] The functional group-containing compound is preferably maleic anhydride. Maleic anhydride has high reactivity with the above-mentioned olefin polymer, and has little major structural change due to polymerization, etc., and tends to be stable as a basic structure. Therefore, it has various advantages such as being able to obtain a modified polyolefin resin (B) with stable quality.

[0139] Examples of the method for obtaining the modified polyolefin resin (B) using the ethylene-α-olefin copolymer include a method of subjecting the ethylene-α-olefin copolymer to so-called graft modification with a functional group-containing compound corresponding to the functional group structural unit.

[0140] The density of the modified polyolefin resin (B) is preferably 0.800 to 0.965 g / cm 3 , more preferably 0.820~0.950g / cm 3 , more preferably 0.850~0.920g / cm 3 .

[0141] Furthermore, the intrinsic viscosity [η] of the modified polyolefin resin (B) measured in a decalin (decahydronaphthalene) solution at 135° C. is preferably 1.0 to 4.5 dl / g, more preferably 1.2 to 3 dl / g. When [η] is within the above range, the mechanical strength and injection fluidity of the resin composition can be achieved at a high level.

[0142] The [η] of the modified polyolefin resin (B) at 135°C in decalin can be measured as follows based on a conventional method. 20 mg of the sample is dissolved in 15 ml of decalin, and the specific viscosity (ηsp) is measured in an atmosphere of 135°C using an Ubbelohde viscometer. After further dilution by adding 5 ml of decalin to the decalin solution, the same specific viscosity measurement is performed. Based on the measurement results of repeating the dilution operation and viscosity measurement two more times, the "ηsp / C" value when the concentration (C) is extrapolated to zero is set as the intrinsic viscosity [η].

[0143] The melt flow rate (MFR, according to JIS K7210, temperature 190°C, load 21.2N) of the modified polyolefin resin (B) is preferably 0.01 to 20 g / 10 minutes, more preferably 0.05 to 20 g / 10 minutes, and further preferably 0.1 to 10 g / 10 minutes. When the MFR is less than 0.01 g / 10 minutes, the fluidity is poor, and when it exceeds 20 g / 10 minutes, the impact strength may be reduced depending on the shape of the molded body.

[0144] The content of modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of polyamide resin (A) and modified polyolefin resin (B). When the above content is 4.70% by mass or more, the air tightness of the metal resin joint body in the initial stage and when the hot and cold shock is repeatedly applied can be improved. When the above content is 20.00% by mass or less, a sufficient amount of polyamide resin (A) can be combined in the resin composition to give full play to the various characteristics of the polyamide resin. From the above viewpoint, the content of modified polyolefin resin (B) is preferably 4.70% by mass or more and 12.50% by mass or less, more preferably 4.70% by mass or more and 8.00% by mass or less. By making the content of modified polyolefin resin (B) be 8.00% by mass or less, the molding processability of the resin composition can be improved, and a molded product with excellent mechanical properties such as tensile strength can be formed.

[0145] 1-3. Nucleating agent (C)

[0146] The polyamide resin composition contains a nucleating agent (C) in addition to the polyamide resin (A) and the modified polyolefin resin (B). The nucleating agent (C) can promote the crystallization of the polyamide resin (A). The nucleating agent (C) promotes the crystallization of the polyamide resin (A) in the resin composition impregnated in the concave portion on the surface of the metal component during the molding process of the resin component, thereby improving the crystallinity of the resin component. Thus, the bonding strength between the metal component and the resin component can be improved.

[0147] When the polyamide resin composition also contains nucleating agent (C) in addition to the polyamide resin (A), as mentioned above, the crystallinity of the resin component obtained by molding the polyamide resin composition is improved. If the crystallinity of the resin component becomes higher, there is a tendency that the elongation of the resin component decreases. However, when the metal resin joint body formed by joining the metal component and the resin component is given a temperature change, due to the difference in the thermal expansion coefficient (linear expansion coefficient) of the metal component and the resin component, stress is generated at the interface between the metal component and the resin component. At this time, if the elongation of the resin component is low, it is possible to peel off at the interface between the metal component and the resin component, or cause the resin component to crack due to compressive stress. Therefore, when the polyamide resin composition only contains nucleating agent (C) in addition to the polyamide resin (A), although the bonding strength of the metal resin joint body is improved, on the other hand, the airtightness when repeatedly applying hot and cold shocks is likely to be reduced.

[0148] On the other hand, the polyamide resin composition of the present embodiment also contains a modified polyolefin resin (B) in addition to the polyamide resin (A) and the nucleating agent (C). As mentioned above, the modified polyolefin resin (B) reduces the elastic modulus of the polyamide resin composition and imparts flexibility to the resin member. It is believed that the airtightness during repeated application of thermal shocks can be better maintained by making the resin member soft. Therefore, it is believed that the polyamide resin composition of the present embodiment can take into account the maintenance of high bonding strength and airtightness during repeated application of thermal shocks by containing a nucleating agent (C) and a modified polyolefin resin (B).

[0149] In addition, when the polyamide resin composition also contains a modified polyolefin resin (B) in addition to the polyamide resin (A), as mentioned above, the crystallization rate of the polyamide resin composition is reduced, and the resin component after molding is given flexibility. If the content of the modified polyolefin resin (B) is increased, the flexibility of the resin component after molding is further improved, and as a result, the airtightness when repeatedly applying hot and cold shocks can be further well maintained. But, on the other hand, the reduction of the crystallization rate of the polyamide resin composition is also promoted, the crystallinity of the resin component after molding is reduced, and the bonding strength of the metal component and the resin component can be reduced. In this way, in the polyamide resin composition of the system of adding the modified polyolefin resin (B), there is a relationship of one increase and the other decrease between the bonding strength of the metal component and the resin component and the airtightness when repeatedly applying hot and cold shocks, which is difficult to take into account.

[0150] On the other hand, the polyamide resin composition of the present embodiment contains a nucleating agent (C) in addition to the polyamide resin (A) and the modified polyolefin resin (B). The present inventors have found that the above-mentioned trade-off relationship can be broken by adding a nucleating agent (C). That is, by adding a nucleating agent (C), the polyamide resin composition containing a predetermined amount of modified polyolefin resin (B) can improve the bonding strength between the metal component and the resin component while maintaining high airtightness when repeatedly subjected to thermal shock.

[0151] Examples of nucleating agents include metal salt compounds including sodium 2,2-methylenebis(4,6-di-tert-butylphenyl)phosphate, aluminum tri(p-tert-butylbenzoate) and stearate, sorbitol compounds including bis(p-methylbenzylidene)sorbitol and bis(4-ethylbenzylidene)sorbitol, and inorganic substances including talc, calcium carbonate and hydrotalcite. Among them, talc is preferred from the viewpoint of further improving the crystallinity of the molded body. These nucleating agents may be used alone or in combination of two or more.

[0152] Talc is usually composed of hydrated magnesium silicate (SiO2: 58-64%, MgO: 28-32%, Al2O3: 0.5-5%, Fe2O3: 0.3-5%) as the main component. The average particle size of talc is not particularly limited, and is preferably 1-15 μm. When the average particle size of talc is within the above range, it is easy to disperse talc in the polyamide resin (A) without damaging the fluidity of the polyamide resin composition. From the same point of view, the average particle size of talc is more preferably 1-7.5 μm. The average particle size of talc can be measured by laser diffraction method, for example, using the laser diffraction method of the Shimadzu particle size distribution measuring instrument SALD-2000 A type manufactured by Shimadzu Corporation (Strain).

[0153] The content of the nucleating agent is preferably 0.10 parts by mass or more and 5.00 parts by mass or less, and more preferably 0.10 parts by mass or more and 3.00 parts by mass or less relative to the total mass of the polyamide resin composition. When the content of the nucleating agent is within the above range, it is easy to sufficiently increase the crystallinity of the molded body and to obtain sufficient mechanical strength.

[0154] 1-4. Other ingredients

[0155] The polyamide resin composition may contain other known components.

[0156] Examples of other components include lubricants, colorants, reinforcing materials, heat stabilizers, corrosion resistance enhancers, anti-drip agents, ion scavengers, elastomers (rubbers), antistatic agents, mold release agents, antioxidants (phenols, amines, sulfurs, phosphorus, etc.), heat stabilizers other than the above (lactone compounds, vitamin E, hydroquinones, etc.), light stabilizers (benzotriazoles, triazines, benzophenones, benzoates, hindered amines, oxanilides, etc.), other polymers (polyolefins, olefin copolymers such as ethylene-propylene copolymers, ethylene-1-butene copolymers, olefin copolymers such as propylene-1-butene copolymers, polystyrene, polyamide, polycarbonate, polyacetal, polysulfone, polyphenylene ether, fluororesin, silicone resin, LCP, etc.), etc. Among them, from the viewpoint of improving the mechanical strength of the molded body, the polyamide resin composition constituting the resin member preferably further contains a reinforcing material.

[0157] 1-4-1. Lubricant

[0158] The lubricant improves the injection fluidity of the polyamide resin composition and improves the appearance of the obtained molded article. The lubricant may be a fatty acid metal salt such as a hydroxycarboxylic acid metal salt and a higher fatty acid metal salt.

[0159] The hydroxycarboxylic acid constituting the above-mentioned hydroxycarboxylic acid metal salt may be an aliphatic hydroxycarboxylic acid or an aromatic hydroxycarboxylic acid. Examples of the above-mentioned aliphatic hydroxycarboxylic acid include aliphatic hydroxycarboxylic acids having a carbon number of 10 or more and 30 or less, such as α-hydroxymyristic acid, α-hydroxypalmitic acid, α-hydroxystearic acid, α-hydroxyeicosanoic acid, α-hydroxyeicosanoic acid, α-hydroxytetracosanoic acid, α-hydroxyhexacosanoic acid, α-hydroxyoctacosanoic acid, α-hydroxytriacontanoic acid, β-hydroxymyristic acid, 10-hydroxydecanoic acid, 15-hydroxypentadecanoic acid, 16-hydroxyhexadecanoic acid, 12-hydroxystearic acid and ricinoleic acid. Examples of the above-mentioned aromatic hydroxycarboxylic acid include salicylic acid, m-hydroxybenzoic acid, p-hydroxybenzoic acid, gallic acid, mandelic acid, and tropic acid.

[0160] Examples of the metal constituting the above-mentioned hydroxycarboxylic acid metal salt include alkali metals such as lithium, and alkaline earth metals such as magnesium, calcium, and barium.

[0161] Among them, the hydroxycarboxylic acid metal salt is preferably a metal salt of 12-hydroxystearic acid, and more preferably magnesium 12-hydroxystearate and calcium 12-hydroxystearate.

[0162] Examples of the higher fatty acid constituting the higher fatty acid metal salt include higher fatty acids having 15 to 30 carbon atoms, such as stearic acid, oleic acid, behenic acid, behenic acid, and montanic acid.

[0163] Examples of the metal constituting the above-mentioned higher fatty acid metal salt include calcium, magnesium, barium, lithium, aluminum, zinc, sodium, potassium and the like.

[0164] Among them, the higher fatty acid metal salt is preferably calcium stearate, magnesium stearate, barium stearate, calcium behenate, sodium montanate, calcium montanate, or the like.

[0165] The content of the lubricant is preferably 0.01% by mass or more and 1.30% by mass or less relative to the total mass of the polyamide resin composition. When the content of the lubricant is 0.01% by mass or more, the fluidity during molding is easily improved, and the appearance of the obtained molded product is easily improved. When the content of the lubricant is 1.30% by mass or less, it is difficult to generate gas caused by the decomposition of the lubricant during molding, and the appearance of the product is easy to become good.

[0166] 1-4-2. Colorants

[0167] The colorant imparts a desired color tone to the molded article. The colorant is not particularly limited and may be a pigment. Examples of pigments include inorganic pigments such as carbon black, aluminum oxide, titanium oxide, chromium oxide, iron oxide, zinc oxide, and barium sulfate; and organic pigments such as azo pigments, phthalocyanine pigments, quinacridone pigments, perylene pigments, anthraquinone pigments, thioindigo pigments, and indanthrene pigments.

[0168] The content of the colorant is preferably 0.01% by mass or more and 5.00% by mass or less, and more preferably 0.10% by mass or more and 2.00% by mass or less, based on the total mass of the polyamide resin composition.

[0169] 1-4-3. Reinforcement materials

[0170] The reinforcing material can impart high mechanical strength to the polyamide resin composition. The reinforcing material can be an inorganic filler. Examples of reinforcing materials include fibrous reinforcing materials such as glass fiber, wollastonite, potassium titanate whisker, calcium carbonate whisker, aluminum borate whisker, magnesium sulfate whisker, zinc oxide whisker, milled fiber and cut fiber, and granular reinforcing materials. Among them, one can be used alone, or two or more can be used in combination. Among them, from the aspects of easily improving the mechanical strength of the molded body, preferably wollastonite, glass fiber, potassium titanate whisker, more preferably wollastonite or glass fiber.

[0171] From the viewpoint of the moldability of the polyamide resin composition and the mechanical strength and heat resistance of the obtained molded body, the average fiber length of the fibrous reinforcement material can be, for example, 1 μm or more and 20 mm or less, preferably 5 μm or more and 10 mm or less. In addition, the aspect ratio of the fibrous reinforcement material is, for example, 5 or more and 2000 or less, preferably 30 or more and 600 or less.

[0172] The average fiber length and average fiber diameter of the fibrous reinforcement material can be measured by the following method.

[0173] 1) A polyamide resin composition was dissolved in a hexafluoroisopropanol / chloroform solution (0.1 / 0.9% by volume), and then filtered to collect the obtained filtrate.

[0174] 2) The filtrate obtained in 1) above was dispersed in water, and the fiber length (Li) and fiber diameter (di) of 300 random fibers were measured using an optical microscope (magnification: 50 times). The number of fibers having a fiber length of Li was defined as qi, and the weight average length (Lw) was calculated based on the following formula, which was used as the average fiber length of the fibrous reinforcing material.

[0175] Weight average length (Lw) = (Σqi × Li 2 ) / (Σqi×Li)

[0176] Similarly, the number of fibers having a fiber diameter of Di is defined as ri, and the weight average diameter (Dw) is calculated based on the following formula, which is used as the average fiber diameter of the fibrous reinforcing material.

[0177] Weight average diameter (Dw)=(Σri×Di 2 ) / (Σri×Di)

[0178] The content of reinforcing material is not particularly limited, and relative to the gross mass of the polyamide resin composition, for example, can be set to more than 15 mass % and less than 70 mass %. It should be noted that, from the viewpoint of suppressing the reduction of the initial air tightness caused by the fluidity and elastic modulus reduction of the polyamide resin composition caused by adding reinforcing material and the reduction of the air tightness maintenance rate after repeated application of hot and cold shocks, the content of reinforcing material is preferably set to more than 15 mass % and less than 50 mass % relative to the gross mass of the polyamide resin composition. But, even when reinforcing material is added in a large amount, by adjusting the amount of polyamide resin (A), the amount of modified polyolefin resin (B), the maintenance rate of the air tightness after initial air tightness and repeated application of hot and cold shocks can be fully improved.

[0179] 1-4-4. Heat-resistant stabilizer

[0180] Heat-resistant stabilizers can improve the fluidity of the polyamide resin composition during the molding of the resin component. Thus, the polyamide resin composition constituting the resin component can be fully flowed along the concavo-convex of the metal component surface, so that the polyamide resin composition is fully close to the above-mentioned concavo-convex. Therefore, it is believed that heat-resistant stabilizers can further improve the bonding strength between the metal component and the resin component, and further improve air tightness.

[0181] The heat resistant stabilizer comprises (i) a salt of a halogen and a metal element of Group 1 or Group 2 of the periodic table (halogen metal salt) and (ii) a copper compound, and may further comprise (iii) a higher fatty acid metal salt as required.

[0182] (i) Examples of the halogen metal salt include potassium iodide, potassium bromide, potassium chloride, sodium iodide and sodium chloride. Among them, potassium iodide and potassium bromide are preferred. The halogen metal salt may contain only one kind or two or more kinds.

[0183] (ii) Examples of copper compounds include copper halides, copper salts (sulfates, acetates, propionates, benzoates, adipates, terephthalates, salicylates, nicotinates, and stearates), and copper chelate compounds (compounds of copper and ethylenediamine or ethylenediaminetetraacetic acid). Among them, copper iodide, cuprous bromide, cupric bromide, cuprous chloride, and cupric acetate are preferred. The copper compound may be contained alone or in combination of two or more.

[0184] Regarding the mass ratio of (i) the halogen metal salt to (ii) the copper compound, from the viewpoint of easily improving the heat resistance of the molded body and the corrosiveness during production, the molar ratio of the halogen to the copper can be adjusted to 0.1 / 1 to 200 / 1, preferably 0.5 / 1 to 100 / 1, and more preferably 2 / 1 to 40 / 1.

[0185] (iii) Examples of higher fatty acid metal salts include higher saturated fatty acid metal salts and higher unsaturated fatty acid metal salts.

[0186] The higher saturated fatty acid metal salt is preferably a metal salt of a saturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as an element of Group I, II, or III of the periodic table, zinc, or aluminum. Such a higher saturated fatty acid metal salt is represented by the following formula (1).

[0187] CH3(CH2) n COO(M1)···(1)

[0188] (In formula (1), the metal element (M1) is an element of the first, second or third group of the periodic table, zinc or aluminum, and n can be 8 to 30.)

[0189] Examples of higher saturated fatty acid metal salts include lithium, sodium, magnesium, calcium, zinc and aluminum salts of capric acid, undecanoic acid, lauric acid, tridecanoic acid, myristic acid, pentadecanoic acid, palmitic acid, heptadecanoic acid, stearic acid, nonadecanoic acid, arachidic acid, behenic acid, lignoceric acid, cerotic acid, heptacosanoic acid, montanic acid, melissic acid and dotriacontanoic acid.

[0190] The higher unsaturated fatty acid metal salt is preferably a metal salt of an unsaturated fatty acid having 6 to 22 carbon atoms and a metal element (M1) such as an element of Group I, II, or III of the periodic table, zinc, or aluminum.

[0191] Examples of metal salts of higher unsaturated fatty acids include lithium, sodium, magnesium, calcium, zinc and aluminum salts of undecenoic acid, oleic acid, elaidic acid, cetylene acid, erucic acid, brassylene acid, sorbic acid, linoleic acid, linolenic acid, arachidonic acid, stearic acid, 2-hexadecenoic acid, 7-hexadecenoic acid, 9-hexadecenoic acid, gadoleic acid, gadelaidic acid and 11-eicosenoic acid.

[0192] Examples of the copper-based heat stabilizer include a mixture of 10% by mass of cuprous iodide and 90% by mass of potassium iodide, a mixture of 14.3% by mass of cuprous iodide and 85.7% by mass of potassium iodide / calcium distearate (98:2 mass ratio), and the like.

[0193] It should be noted that, according to the knowledge of the present inventors, copper-based heat stabilizers sometimes generate gas when thermal shock is repeatedly applied, thereby sometimes reducing the airtightness maintenance rate. From the viewpoint of suppressing the reduction of airtightness when thermal shock is repeatedly applied, the content of the copper-based heat stabilizer is preferably set to 0.30% by mass or less, more preferably 0.10% by mass or less, and more preferably less than 0.01% by mass relative to the total mass of the polyamide resin composition.

[0194] 1-5. Manufacturing method

[0195] The polyamide resin composition can be produced by a known resin kneading method, for example, by mixing the aforementioned polyamide resin and other components as required using a Henschel mixer, a V-type mixer, a ribbon mixer or a tumble mixer, or by further melt-kneading the mixed components using a single-screw extruder, a multi-screw extruder, a kneader or a Banbury mixer and then granulating or pulverizing the components.

[0196] 2. Metal-resin joint

[0197] A second embodiment of the present invention relates to a metal-resin joined body in which a resin member made of the polyamide resin composition is joined to a surface of a metal member.

[0198] 2-1. Resin components

[0199] The resin component comprises the polyamide resin composition. Relative to the total mass of the resin component, the proportion of the polyamide resin composition is preferably 50.00% by mass or more, more preferably 60.00% by mass or more, and further preferably 70.00% by mass or more. Relative to the total mass of the resin component, the upper limit of the proportion of the polyamide resin composition is not particularly limited, and can be set to 100.00% by mass or less, can be 90.00% by mass or less, and can also be 80.00% by mass or less.

[0200] 2-2.Metal components

[0201] The metal component can be any metal component, and its material and shape are not particularly limited. For example, the material of the metal component can be iron, copper, nickel, gold, silver, platinum, cobalt, zinc, lead, tin, titanium, chromium, aluminum, magnesium, manganese, stainless steel, brass, phosphor bronze and other alloys.

[0202] These materials can be selected according to the purpose of the metal-resin joint body. For example, when thermal conductivity is required, aluminum, aluminum alloy, magnesium, magnesium alloy, copper and copper alloy are preferred, and copper and copper alloy are more preferred. In addition, when lightweighting and ensuring strength are required, aluminum, aluminum alloy, magnesium and magnesium alloy are preferred.

[0203] The surface of the metal member is preferably roughened. The method of surface roughening is not particularly limited, and the surface may be roughened by immersion in a treatment solution containing an alkali or an acid, chemical treatment such as etching, or physical treatment such as laser or sandblasting.

[0204] In the surface of the metal component after surface roughening, the center-to-center distance (pitch) of the multiple protrusions formed by the surface roughening treatment is preferably greater than 5nm and less than 500μm. If the center-to-center distance of the multiple protrusions is greater than 5nm, the recesses between the protrusions are moderately large, so it is easy to fully immerse the resin component in the recess during bonding, which can further improve the bonding strength between the metal component and the resin component. In addition, if the center-to-center distance of the multiple protrusions is less than 500μm, the recess will not become too large, so it is possible to further suppress the formation of gaps at the metal-resin interface of the metal-resin joint, further improving the airtightness. From the same point of view, the center-to-center distance of the multiple protrusions is more preferably greater than 5μm and less than 250μm. The center-to-center distance of the multiple protrusions is the average value of the distance between the center of a protrusion and the center of the protrusion adjacent to it.

[0205] The center-to-center distance of the plurality of projections can be measured by removing the resin member from the metal-resin joint by mechanical stripping, solvent washing, or the like, and observing the surface of the exposed metal member with an electron microscope or a laser microscope, or by observing using a surface roughness measuring device.

[0206] Specifically, when the center-to-center distance of the plurality of convex portions is less than 0.5 μm, it can be observed by an electron microscope, and when the center-to-center distance of the plurality of convex portions is greater than 0.5 μm, it can be observed by a laser microscope or a surface roughness measuring device. For example, in a photograph of the surface of a metal component taken with an electron microscope or a laser microscope, 50 arbitrary convex portions are selected, and the center-to-center distances of these convex portions are measured respectively. Then, all measured values ​​of the center-to-center distances of the convex portions are accumulated and divided by 50, and the value thus obtained (average value) is used as the "center-to-center distance of the plurality of convex portions".

[0207] The average value of the ten-point average roughness (Rz) of the surface of the metal component that has been surface roughened in an evaluation length of 4 mm is not particularly limited, but is preferably greater than 2 μm, more preferably greater than 2 μm and less than 50 μm, and further preferably greater than 2.5 μm and less than 45 μm.

[0208] The average value of the ten-point average roughness (Rz) can be measured according to JIS B0601 (ISO 4287). Specifically, the ten-point average roughness (Rz) on a total of six straight line portions, namely, three arbitrary straight line portions parallel to each other and three arbitrary straight line portions orthogonal to them, is measured, and their average value is taken as the average value of Rz.

[0209] In the surface roughened surface of the metal component, the average length (RSm) of the roughness curve element is preferably 0.5 μm or more and 500 μm or less. In particular, from the viewpoint of further improving the bonding strength, it is preferred that the center-to-center distance of the plurality of convex portions is less than 0.5 μm, and the average length (RSm) of the roughness curve element is 0.5 μm or more and 500 μm or less. The average length of the roughness curve element can also be measured according to JIS B0601 (ISO 4287) as described above.

[0210] 3. Method for manufacturing metal-resin joint

[0211] A second embodiment of the present invention relates to a method for producing the metal-resin composite structure. The method for producing the metal-resin composite structure is not particularly limited, and for example comprises: (1) a step of preparing a metal component, (2) a step of bringing a molten polyamide resin composition into contact with a surface of the metal component, and (3) a step of cooling the contacted polyamide resin composition. The above-mentioned step (1) of preparing a metal component may include a step of roughening the surface of the metal component.

[0212] 3-1. Preparation of metal components

[0213] First, the above-mentioned metal member is prepared. At this time, at least a part of the surface of the metal member may be subjected to a surface roughening treatment, or a metal member having a concavo-convex structure on at least a part of the surface may be prepared.

[0214] There is no particular limitation on the method of roughening the surface of the metal component. For example, the following methods may be used: a method using laser processing; a method of immersing the metal component in an aqueous solution of an inorganic base such as NaOH or an aqueous solution of an inorganic acid such as HCl or HNO3; a method of treating the metal component by anodizing; a replacement crystallization method using an acid etchant (preferably an aqueous solution of an acid etchant containing an inorganic acid, trivalent iron ions, divalent cupric ions, and, as required, manganese ions, aluminum chloride hexahydrate, sodium chloride, etc.); a method of immersing the metal component in an aqueous solution of hydrazine hydrate, ammonia, and a water-soluble amine compound; and a warm water treatment method.

[0215] 3-2. Bonding of resin components

[0216] Next, the softened or melted polyamide resin composition is brought into contact with the surface of the metal member prepared above (preferably the surface subjected to the surface roughening treatment).

[0217] The contact method is not particularly limited, and it can be carried out by known methods such as injection molding (insert molding). For example, the prepared metal component is arranged in the cavity portion (space portion) in the injection molding mold. Then, the polyamide resin composition is injected into the cavity portion of the mold in a manner that at least a portion of the polyamide resin composition contacts the surface of the metal component after surface roughening treatment. Thus, the injected molten polyamide resin composition contacts the surface of the metal component. The temperature of the injection molding mold at this time is not particularly limited as long as it can melt the polyamide resin composition to a state suitable for injection molding, and can be set to 100~350°C, for example.

[0218] As the mold, a known injection molding mold, for example, a mold for high-speed heat cycle molding (RHCM, heating & cooling molding) or a core-back mold for foam molding can be used.

[0219] 3-3. Cooling

[0220] Then, the polyamide resin composition in contact with the surface of the metal member is cooled and solidified, thereby obtaining a metal-resin joint body in which the resin member including the polyamide resin composition is joined to the surface of the metal member.

[0221] 4. Purpose

[0222] The above-mentioned metal-resin bonded body is suitable for various applications to which the metal-resin bonded body is applied or to which the application of the metal-resin bonded body is being studied.

[0223] Examples of the above-mentioned uses include structural parts for vehicles, vehicle-mounted products, housings of electronic devices, housings of home appliances, structural parts, mechanical parts, various automotive parts, electronic equipment parts, furniture, kitchen supplies and other home-oriented uses, medical equipment, parts of building materials, other structural parts and exterior parts, etc.

[0224] More specifically, in the above-mentioned examples of use, vehicle-related components include instrument panels, console boxes, door handles, door trims, gear levers, pedals, glove boxes, bumpers, engine hoods, fenders, trunks, doors, roofs, pillars, seats, steering wheels, busbars, terminals, motors, power conversion devices (inverters, converters), ECU boxes, electrical components, engine peripheral components, drive system / gear peripheral components, intake / exhaust system components, and cooling system components, etc. In addition, precision electronic components include connectors, relays, gears, etc.

[0225] In addition, the metal-resin joint body can also be used for components used in equipment designed to optimize thermal management by combining the high thermal conductivity of the copper component with the thermal insulation properties of the resin component, such as various home appliances. Examples of the above-mentioned uses include home appliances such as refrigerators, washing machines, vacuum cleaners, microwave ovens, air conditioners, lighting equipment, electric water heaters, televisions, clocks, ventilators, projectors, speakers, personal computers, mobile phones, smart phones, digital cameras, tablet PCs, portable music players, portable game consoles, chargers, batteries, and other electronic information devices.

[0226] Examples of other applications include components for lithium-ion secondary batteries and robots.

[0227] For example, the metal-resin joint body can be used for a bus bar unit of a mobile body (vehicle) such as an automobile.

[0228] Figure 1 The figure is a schematic diagram showing an exemplary form of the metal-resin joint body as a bus bar unit. The bus bar unit 100 includes: a bus bar 110 which is a conductive metal member (e.g., a copper metal member) for supplying current to each member; and a retaining member 120 which is a protective member for protecting the bus bar 110 as the resin member.

[0229] The surface of the busbar 110 as a metal member that contacts the retaining member 120 is roughened, and the retaining member 120 as a resin member (a resin member formed of a polyamide resin composition) is bonded to the roughened surface.

[0230] The bus bar unit 100 can be used to electrically connect a motor of a moving object and an inverter for controlling electric power supplied to the motor through the bus bar 110 .

[0231] Figure 2 1 is a block diagram showing an exemplary structure of a moving object (vehicle) having the bus bar unit 100. The moving object 200 has a body 210, a power source 220 such as a secondary battery that supplies power for driving the body 210, and a drive unit 230 that drives the body 210 with the power supplied from the power source 220.

[0232] The drive unit 230 includes an inverter 232 that controls the power (current) from the power source 220, a motor 234 that rotates when supplied with the power controlled by the inverter 232, and a bus bar unit 100 that includes a bus bar 110 that connects the inverter 232 and the motor 234. The motor 234 is housed in a motor housing 236 together with a speed reducer 235 that converts the rotation speed obtained by the motor 234 into a rotation speed for driving the machine body 210. The bus bar unit 100 is mounted on the motor housing 236, and the bus bar 110 is connected from the inside of the motor housing 236 to the outside via the bus bar unit 100.

[0233] It should be noted that the motor housing 236 stores a coolant (cooling oil) for cooling the motor 234. In addition, the connection between the bus bar unit 100 and the motor housing 236 is airtightly treated by a sealing member such as an O-ring, thereby preventing oil from leaking from the inside of the motor housing 236 to the outside.

[0234] However, in the conventional busbar unit, when the thermal shock caused by the heat of the motor 234 is repeatedly applied, the airtightness between the busbar and the resin protective member is sometimes reduced, and oil leaks from between the busbar and the protective member. In contrast, in the present embodiment, since the retaining member 120 composed of the resin member of the molded body including the above-mentioned polyamide resin composition is joined to the busbar 110 as a conductive metal member (for example, a copper metal member), even if the thermal shock caused by the heat of the motor 234 is repeatedly applied, the airtightness maintenance rate is high, and the oil leakage can be suppressed for a long time.

[0235] It should be noted that in Figure 2 2 shows an example in which the moving body 200 is a vehicle such as a car, but the moving body 200 is not particularly limited as long as it has a body and a drive unit and can move. For example, in addition to vehicles such as cars, motorcycles, and electric bicycles, railway vehicles, ships, airplanes, drones, robots, etc. can also be used as the moving body 200.

[0236] Example

[0237] Hereinafter, the present invention will be described with reference to Examples, but the scope of the present invention should not be construed as being limitative due to the Examples.

[0238] In addition, in the following experiments, the physical properties of each resin were measured by the following methods.

[0239] (Melting point (Tm), glass transition temperature (Tg))

[0240] The melting point (Tm) and glass transition temperature (Tg) of the polyamide resin are measured using differential scanning calorimetry (DSC220C type, Seiko Instruments). Specifically, about 5 mg of polyamide resin is sealed in an aluminum pan for measurement and set in differential scanning calorimetry. Then, it is heated to 350°C from room temperature at 10°C / min. In order to completely melt the resin, it is kept at 350°C for 3 minutes, and then cooled to 30°C at 10°C / min. After being placed at 30°C for 5 minutes, it is heated to 350°C for the second time at 10°C / min. The temperature (°C) of the endothermic peak in the second heating is taken as the melting point (Tm) of the polyamide resin, and the displacement point equivalent to the glass transition is taken as the glass transition temperature (Tg).

[0241] (Heat of Fusion (ΔH))

[0242] The heat of fusion (ΔH) of the polyamide resin was determined from the area of ​​the exothermic peak of crystallization in the first heating process in accordance with JIS K 7122 (2012).

[0243] (Intrinsic viscosity [η])

[0244] The intrinsic viscosity [η] of the polyamide resin is calculated as follows: 0.5 g of the polyamide resin is dissolved in 50 ml of a 96.5% sulfuric acid solution, and the flow time of the resulting solution at 25°C±0.05°C is measured using an Ubbelohde viscometer. The intrinsic viscosity [η] is calculated based on the mathematical formula: [η]=ηSP / (C(1+0.205ηSP))".

[0245] [η]: Intrinsic viscosity (dl / g)

[0246] ηSP: specific viscosity

[0247] C: Sample concentration (g / dl)

[0248] t: Number of seconds for the sample solution to flow down (seconds)

[0249] t0: Number of seconds for blank sulfuric acid to flow (seconds)

[0250] ηSP=(t-t0) / t0

[0251] (composition)

[0252] The composition of the modified polyolefin resin, specifically, the content (mol %) of ethylene and α-olefin having 3 or more carbon atoms, and the content (mass %) of the functional group structural unit are determined by 13 The measurement conditions are as follows.

[0253] Measurement device: Nuclear magnetic resonance device (ECP500, manufactured by JEOL Ltd.)

[0254] Observation core: 13 C(125 MHz)

[0255] Sequence: Single Pulse Decoupling

[0256] Pulse width: 4.7μs (45° pulse)

[0257] Repeat time: 5.5 seconds

[0258] Cumulative times: more than 10,000 times

[0259] Solvent: o-dichlorobenzene / deuterated benzene (volume ratio: 80 / 20) mixed solvent

[0260] Sample concentration: 55mg / 0.6mL

[0261] Measuring temperature: 120℃

[0262] Chemical shift reference value: 27.50ppm

[0263] (density)

[0264] The density of the modified polyolefin resin was measured at a temperature of 23° C. using a density gradient tube in accordance with JIS K7112.

[0265] (Melt Flow Rate (MFR))

[0266] The melt flow rate (MFR) of the modified polyolefin resin is measured at 190° C. and a load of 2.16 kg in accordance with ASTM D1238. The unit is g / 10 min.

[0267] (Melting Point)

[0268] The melting point of the modified polyolefin resin is measured by differential scanning calorimetry (DSC).

[0269] 1. Synthesis / Preparation of Materials

[0270] 1-1. Synthesis of polyamide resin (A)

[0271] 1-1-1. Polyamide resin (A-1)

[0272] 2800g (24.1 mol) of 1,6-hexanediamine, 2774g (16.7 mol) of terephthalic acid, 1196g (7.2 mol) of isophthalic acid, 36.6g (0.30 mol) of benzoic acid, 5.7g of sodium hypophosphite monohydrate and 545g of distilled water were placed in an autoclave with a content of 13.6L and replaced with nitrogen. Stirring was started from 190°C and the internal temperature was raised to 250°C in 3 hours. At this time, the internal pressure of the autoclave was raised to 3.03MPa. After continuing the reaction for 1 hour in this state, the low-level condensation product was released into the atmosphere from the spray nozzle set at the bottom of the autoclave and taken out. Then, the low-level condensation product was cooled to room temperature, crushed to a particle size of less than 1.5mm by a pulverizer, and dried at 110°C for 24 hours. The moisture content of the obtained low-level condensation product was 4100ppm and the intrinsic viscosity [η] was 0.15dl / g.

[0273] Next, the low-order condensate was placed in a tray-type solid phase polymerization apparatus, and after nitrogen substitution, the temperature was raised to 180°C over about 1 hour and 30 minutes. Then, the reaction was allowed to proceed for 1 hour and 30 minutes, and the temperature was lowered to room temperature. The intrinsic viscosity [η] of the obtained prepolymer was 0.20 dl / g.

[0274] The obtained prepolymer was then melt polymerized using a twin-screw extruder with a screw diameter of 30 mm and L / D=36 at a barrel setting temperature of 330°C, a screw speed of 200 rpm, and a resin supply rate of 6 kg / h to obtain a polyamide resin (A-1).

[0275] The obtained polyamide resin (A-1) had an intrinsic viscosity of 1.0 dl / g, a melting point (Tm) of 330°C, a glass transition temperature (Tg) of 125°C, and a heat of fusion (ΔH) of 50 J / g.

[0276] 1-1-2. Polyamide resin (A-2)

[0277] A polyamide resin (A-2) was obtained in the same manner as in the synthesis of the polyamide resin (A-1) except that the raw materials were changed to 2184 g (13.1 mol) of terephthalic acid, 2800 g (24.1 mol) of hexamethylenediamine, and 1572 g (10.8 mol) of adipic acid.

[0278] The obtained polyamide resin (A-2) had an intrinsic viscosity [η] of 0.8 dl / g, a melting point (Tm) of 310°C, a glass transition temperature (Tg) of 85°C, and a heat of fusion (ΔH) of 50 J / g.

[0279] 1-1-3. Polyamide resin (A-3)

[0280] A polyamide resin (A-3) was obtained in the same manner as in the synthesis of the polyamide resin (A-1) except that the raw materials were changed to 1720 g (10.4 mol) of terephthalic acid, 2800 g (24.1 mol) of hexamethylenediamine, and 1849 g (12.7 mol) of adipic acid.

[0281] The obtained polyamide resin (A-3) had an intrinsic viscosity [η] of 0.9 dl / g, a melting point (Tm) of 295°C, a glass transition temperature (Tg) of 75°C, and a heat of fusion (ΔH) of 60 J / g.

[0282] 1-1-4. Polyamide resin (A-4)

[0283] A polyamide resin (A-4) was obtained in the same manner as in the synthesis of the polyamide resin (A-1) except that the raw materials were changed to 3655 g (22.0 mol) of terephthalic acid, 1312 g (11.3 mol) of 1,6-diaminohexane, and 1312 g (11.3 mol) of 2-methyl-1,5-diaminopentane.

[0284] The obtained polyamide resin (A-4) had an intrinsic viscosity [η] of 0.9 dl / g, a melting point (Tm) of 300°C, a glass transition temperature (Tg) of 140°C, and a heat of fusion (ΔH) of 40 J / g.

[0285] 1-1-5. Polyamide resin (A-5)

[0286] UBESTA 3014B manufactured by Ube Industries, Ltd. was used as the polyamide resin (A-5).

[0287] The polyamide resin (A-5) had an intrinsic viscosity [η] of 0.54 dl / g, a melting point (Tm) of 180°C, a glass transition temperature (Tg) of 50°C, and a heat of fusion (ΔH) of 60 J / g.

[0288] 1-1-6. Polyamide resin (A-6)

[0289] A polyamide resin (A-6) was obtained in the same manner as in the synthesis of the polyamide resin (A-1) except that the raw materials were changed to 2774 g (16.7 mol) of isophthalic acid, 2800 g (24.1 mol) of 1,6-diaminohexane, and 1196 g (7.2 mol) of terephthalic acid.

[0290] The intrinsic viscosity [η] of the obtained polyamide resin (A-6) was 0.54 dl / g, the melting point (Tm) could not be measured, the glass transition temperature (Tg) was 125°C, and the heat of fusion (ΔH) was 0 J / g.

[0291] 1-2. Synthesis of modified polyolefin resin (B)

[0292] 0.63 mg of bis(1,3-dimethylcyclopentadienyl)zirconium dichloride was added to a glass flask fully purged with nitrogen, and 1.57 ml of a toluene solution of methylaluminoxane (Al; 0.13 mmol / L) and 2.43 ml of toluene were further added to obtain a catalyst solution. Next, 912 ml of hexane and 320 ml of 1-butene were introduced into a stainless steel autoclave with a volume of 2 liters fully purged with nitrogen, and the temperature in the system was raised to 80°C. Next, 0.9 mmol of triisobutylaluminum and 2.0 ml of the catalyst solution prepared above (0.0005 mmol in terms of Zr) were pressed into the system with ethylene to start the polymerization reaction. The total pressure was maintained at 8.0 kg / cm2-G by continuously supplying ethylene, and the polymerization was carried out at 80°C for 30 minutes. After a small amount of ethanol was introduced into the system to stop the polymerization, the unreacted ethylene was purged. A white solid was precipitated by putting the obtained solution into a large excess of methanol. The white solid was recovered by filtration and dried overnight under reduced pressure to obtain a white solid (ethylene-1-butene copolymer).

[0293] The ethylene content of the ethylene-1-butene copolymer was 81 mol %. The density was 0.860 g / cm 3 , MFR (ASTM D 1238, 190°C, 2.16 kg load) is 0.5 g / 10 minutes, and the melting point is 35°C.

[0294] 100 parts by mass of the obtained ethylene-1-butene copolymer was mixed with 1.0 parts by mass of maleic anhydride and 0.04 parts by mass of peroxide (PERHEXYNE 25B, a trademark of NOF Corporation) and the obtained mixture was melt graft-modified using a twin-screw extruder set at 230° C. to obtain a modified polyolefin resin (B).

[0295] The amount of maleic anhydride grafted into the modified polyolefin resin (B) was 0.8% by mass. The density was 0.866 g / cm 3 , MFR (ASTM D 1238, 190°C, 2.16 kg load) is 0.27 g / 10 minutes, and the melting point (Tm) is 35°C.

[0296] 1-3. Other ingredients

[0297] 1-3-1. Nucleating agent (C)

[0298] Talc (average particle size 6 μm) was used as a nucleating agent.

[0299] 1-3-2. Lubricant

[0300] Sodium montanate was used as a lubricant.

[0301] 1-3-3. Colorants

[0302] A masterbatch containing pigment is used as a colorant.

[0303] 1-3-4. Reinforcement materials

[0304] Glass fiber (manufactured by Owens Corning, FT2A) was used as a reinforcing material.

[0305] 1-3-5. Copper-based heat stabilizer

[0306] A mixture of 10 mass % of cuprous iodide and 90 mass % of potassium iodide was used as a copper-based heat stabilizer.

[0307] 2. Fabrication of metal-resin joints

[0308] 2-1. Preparation of polyamide resin composition

[0309] The above materials were mixed in a drum mixer at the composition ratio (parts by mass) shown in Table 1, and melt-kneaded using a 30 mm φ vented twin-screw extruder at a barrel temperature of 300 to 335° C. The kneaded product was then extruded into a strand and cooled in a water tank. The strand was then pulled and cut using a pelletizer to obtain a pelletized polyamide resin composition.

[0310] 2-2. Fabrication of copper components with surface roughening treatment

[0311] A copper alloy plate (thickness 2 mm) of alloy number C1100 specified in JIS H3100: 2012 was cut into pieces of 45 mm in length and 18 mm in width to produce a copper component. The copper component after degreasing was immersed in a chemical etchant (Amalpha A-10201H manufactured by MEC Co., Ltd.), washed with water, and immersed in a chemical etchant in sequence. Immediately thereafter, the component was immersed in a chemical etchant for 4 minutes. Next, water washing, alkali washing (5 mass % NAOH, immersed for 20 seconds), water washing, neutralization treatment (5 mass % H2SO4, immersed for 20 seconds), water washing, rust prevention treatment (A-10290, 1 minute) and water washing were carried out in sequence.

[0312] 2-3. Fabrication of Metal-Resin Joints

[0313] The copper component with a roughened surface was placed in a small dumbbell metal insert mold installed in an injection molding machine (manufactured by Nippon Steel Works, Ltd., J55-AD). Then, the various polyamide resin compositions were injection molded in the mold under the conditions of a barrel temperature of 335°C, a mold temperature of 170°C, a primary injection pressure of 90MPa, a holding pressure of 80MPa, and an injection speed of 25mm / sec to produce a test piece in which a resin component made of polyamide resin was bonded to the surface of the copper component. The bonding area between the copper component and the resin component of the test piece was 50mm 2 .

[0314] 3. Evaluation

[0315] The obtained metal-resin joints were evaluated according to the following criteria.

[0316] 3-1. Airtightness (initial)

[0317] The helium leakage of the prepared test piece was evaluated by the method according to ISO19095. Specifically, the test piece was set in a special fixture that could be sealed, He gas was applied to the sealed space at a pressure of 0.1 MPa, and the He gas passing through the test piece was measured by a He gas detector (HELEN M-222 LD manufactured by Canon ANELVA Co., Ltd.) using a sniffer method. Based on the measured He gas flow rate (leakage) 5 minutes after the start of the test, the airtightness was evaluated according to the following criteria.

[0318] ◎ The measured He gas flow rate is 1×10 -6 Pa·m 3 / s or less

[0319] ○ The measured He gas flow rate is greater than 1×10 -6 Pa·m 3 / s and 1×10 -5 ·m 3 / s or less

[0320] × The measured He gas flow rate is greater than 1×10 -5 Pa·m 3 / s.

[0321] 3-2. Airtightness (after thermal shock test (500 times, 1000 times))

[0322] The He leakage of the prepared test piece after the thermal shock test was evaluated using a method based on ISO19095. Specifically, the prepared test piece was subjected to a thermal shock test using a cooling and heating cycle based on the following conditions, and the subsequent helium leakage was measured in the same manner as the initial airtightness evaluation described above. The airtightness after the thermal shock test was also evaluated using the same criteria as the airtightness (initial).

[0323] (Conditions for thermal shock test)

[0324] Temperature range: -40℃~150℃

[0325] Cycling conditions: 1 cycle of -40°C and 150°C for 30 minutes each

[0326] Cycle times: 500 times, 1000 times

[0327] 3-3. Liquidity

[0328] Each polyamide resin composition was injection-molded under the following conditions using a rod flow mold having a width of 10 mm and a thickness of 0.5 mm, and the flow length (mm) of the resin composition in the mold was measured.

[0329] Injection molding machine: Sodick Plastic Co., Ltd., TUPARL TR40S3A

[0330] Injection setting pressure: 2000kg / cm 2

[0331] Cylinder setting temperature: melting point of polyamide resin + 10°C

[0332] Mold temperature: 160°C (Examples 1 to 3, Examples 6 to 10, Comparative Examples 1 to 5), 120°C (Examples 4 and 5)

[0333] 3-4. Tensile strength

[0334] Each polyamide resin composition was injection-molded under the following conditions to obtain an ISO dumbbell-shaped test piece A type having a thickness of 4.0 mm.

[0335] Molding machine: SG50M3 manufactured by Sumitomo Heavy Industries, Ltd.

[0336] Molding machine barrel temperature: melting point of polyamide resin + 10°C

[0337] Mold temperature: 160°C (Examples 1 to 3, Examples 6 to 10, Comparative Examples 1 to 5), 120°C (Examples 4 and 5)

[0338] The obtained test piece was left to stand for 24 hours at a temperature of 23° C. in a nitrogen atmosphere. Then, a tensile test was performed in accordance with ASTM D638 at a temperature of 23° C. and a relative humidity of 50% to measure the tensile strength.

[0339] 3-5. Flexural modulus

[0340] Each polyamide resin composition was injection-molded under the following conditions to obtain an ISO dumbbell-shaped test piece A type having a thickness of 4.0 mm.

[0341] Molding machine: Sodick Plastic Co., Ltd., TUPARL TR40S3A

[0342] Molding machine barrel temperature: melting point of polyamide resin + 10°C

[0343] Mold temperature: 160°C (Examples 1 to 3, Examples 6 to 10, Comparative Examples 1 to 5), 120°C (Examples 4 and 5)

[0344] The obtained test piece was left to stand for 24 hours in a nitrogen atmosphere at 23°C. Then, a bending test was performed at 23°C and a relative humidity of 50% using a bending tester: AB5 manufactured by NTESCO, with a span of 51 mm and a bending speed of 12.7 mm / min to measure the elastic modulus.

[0345] Tables 1 to 3 show the composition of the prepared polyamide resin composition, the airtightness (initial) and airtightness (after thermal shock test) of the metal-resin joint, and the evaluation results of the flowability, tensile strength and flexural modulus of the polyamide resin composition.

[0346] [Table 1]

[0347]

[0348] [Table 2]

[0349]

[0350] [Table 3]

[0351]

[0352] It can be seen from Tables 1 to 3 that the polyamide resin composition comprising polyamide resin (A1), polyamide resin (A2), a predetermined amount of modified polyolefin resin (B) and a nucleating agent (C) has excellent airtightness in the initial stage of bonding with metal components and after repeated application of hot and cold shocks.

[0353] This application claims the priority of Japanese Patent Application No. 2022-140105 filed on September 2, 2022. The matters described in the specification, claims, and drawings at the time of filing of the above application are incorporated herein by reference.

[0354] Possibility of Industrial Application

[0355] The polyamide resin composition of the present invention can improve the desired air tightness when a resin component formed by the polyamide resin composition is joined to a metal component and the air tightness after repeated thermal shock. Therefore, it is expected that the present invention will expand the use of metal-resin joints in environments where the temperature changes and in environments where leakage of gas, liquid, etc. becomes a problem, such as the possibility of application in vehicle body parts, etc., and contribute to the further popularization of metal-resin joints.

[0356] Description of Reference Numerals

[0357] 100 bus bar unit, 110 bus bar, 120 holding member, 200 moving body, 210 body, 220 power source, 230 drive unit, 232 inverter, 234 motor, 235 speed reducer, 236 motor housing.

Claims

1. A polyamide resin composition for bonding with a metal member, comprising a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), The polyamide resin (A) comprises a polyamide resin (A1) having a melting point Tm of 280° C. or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion ΔH of 5 J / g or lower as measured by differential scanning calorimetry (DSC). The content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

2. The polyamide resin composition according to claim 1, wherein The content of the modified polyolefin resin (B) is 4.70% by mass or more and 12.50% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

3. The polyamide resin composition according to claim 1 or 2, wherein The content of the copper-based heat stabilizer is 0.30 mass % or less based on the total mass of the polyamide resin composition.

4. The polyamide resin composition according to any one of claims 1 to 3, wherein The polyamide resin (A1) has a component unit (A1a) derived from a dicarboxylic acid and a component unit (A1b) derived from a diamine. The component units (A1a) derived from dicarboxylic acid include component units derived from terephthalic acid and component units derived from isophthalic acid.

5. The polyamide resin composition according to any one of claims 1 to 4, wherein The polyamide resin (A) includes a polyamide resin (A3) having a glass transition temperature Tg of 70° C. or less as measured by differential scanning calorimetry (DSC).

6. The polyamide resin composition according to claim 5, wherein The polyamide resin (A3) has a melting point Tm of 200° C. or less as measured by differential scanning calorimetry (DSC).

7. The polyamide resin composition according to any one of claims 1 to 6, wherein The polyamide resin (A1) has a glass transition temperature Tg of 75° C. or higher and 160° C. or lower as measured by differential scanning calorimetry (DSC). The polyamide resin (A2) has a glass transition temperature Tg of 75° C. or higher and 160° C. or lower as measured by differential scanning calorimetry (DSC).

8. The polyamide resin composition according to any one of claims 1 to 7, wherein The nucleating agent (C) is talc, The content of the nucleating agent (C) is 0.10 to 5.00 mass % relative to the total mass of the polyamide resin composition.

9. A metal-resin joint body comprising a metal member and a resin member comprising a polyamide resin composition joined to a surface of the metal member, The polyamide resin composition comprises a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), The polyamide resin (A) comprises a polyamide resin (A1) having a melting point Tm of 280° C. or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion ΔH of 5 J / g or lower as measured by differential scanning calorimetry (DSC). The content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

10. A method for producing a metal-resin joint, comprising: a step of preparing a metal member, a step of bringing a softened or melted polyamide resin composition into contact with a surface of the metal member, and a step of cooling the contacted polyamide resin composition. The polyamide resin composition comprises a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), The polyamide resin (A) comprises a polyamide resin (A1) having a melting point Tm of 280° C. or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion ΔH of 5 J / g or lower as measured by differential scanning calorimetry (DSC). The content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

11. The method for producing a metal-resin joint according to claim 10, wherein: In the step of preparing the metal member, a surface of the metal member to be bonded to the polyamide resin composition is subjected to a surface roughening treatment.

12. A bus bar unit comprising a metal bus bar and a holding member arranged in contact with the bus bar and holding the bus bar, The holding member comprises a polyamide resin (A), a modified polyolefin resin (B) and a nucleating agent (C), wherein the polyamide resin (A) comprises a polyamide resin (A1) having a melting point Tm of 280° C. or higher as measured by differential scanning calorimetry (DSC) and a polyamide resin (A2) having a heat of fusion ΔH of 5 J / g or lower as measured by differential scanning calorimetry (DSC), The content of the modified polyolefin resin (B) is 4.70% by mass or more and 20.00% by mass or less relative to the total mass of the polyamide resin (A) and the modified polyolefin resin (B).

13. A drive unit comprising: a motor, an inverter for supplying electric power to the motor, and a bus bar unit for electrically connecting the motor and the inverter, The bus bar unit is the bus bar unit according to claim 12.

14. A mobile body comprising a body and a driving unit, The drive unit is the drive unit according to claim 13.

Citation Information

Patent Citations

  • Composite of copper and resin

    JP2017132243A

  • Object tracking device and object tracking method

    JP2022140105A